Color filter ink composition, light conversion layer, and color filter
Patent Information
- Application Number
- JP2024205362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-12-16
Smart Images

Figure 2025026476000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for a color filter, a light conversion layer, and a color filter. [Background technology]
[0002] Conventionally, pixel portions (color filter pixel portions) in displays such as liquid crystal display devices have been manufactured by photolithography using a curable resist material containing, for example, red organic pigment particles or green organic pigment particles, and an alkali-soluble resin and / or an acrylic monomer.
[0003] In recent years, there has been a strong demand for lower power consumption in displays, and methods of forming pixel portions such as red pixels and green pixels using luminescent nanocrystal particles such as quantum dots, quantum rods, and other inorganic phosphor particles instead of the above-mentioned red organic pigment particles or green organic pigment particles are being actively researched. In addition to the above-mentioned low power consumption, color filters using these luminescent nanocrystal particles (QD-CF) also have the effect of widening the color reproduction range of displays.
[0004] However, the above-mentioned photolithography-based color filter manufacturing method has a drawback in that the resist material, including the relatively expensive luminescent nanocrystal particles, is wasted in areas other than the pixel area due to the characteristics of the manufacturing method. Under these circumstances, in order to eliminate the waste of the resist material, the formation of the pixel area of the photoconversion substrate by the inkjet method has been considered (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2008 / 001693 Summary of the Invention [Problem to be solved by the invention]
[0006] When applying QD-CF to a display, it is considered to use blue light such as blue LED or blue OLED as the backlight source, and use luminescent nanocrystal particles only in the green and red pixels. In this case, it is known that the half-width of green and red emission is narrower than when using normal organic pigments, so the color reproducibility of the display is improved. On the other hand, in order to improve the color reproducibility of the display, it is necessary to increase the color purity of each pixel, so it is preferable that the blue light originating from the backlight source does not leak from the green and red pixels as much as possible. Generally, green-emitting luminescent nanocrystal particles, which have an emission peak wavelength in the range of 500 to 560 nm, have a lower absorptance of blue light than red-emitting particles, and it is necessary to reduce the leakage of blue light from green pixels.One method for achieving this is to increase the concentration of luminescent nanocrystal particles or the concentration of light diffusing agent in the color conversion layer in the pixel section of the photoconversion substrate. However, particularly when forming the pixel portion of the optical conversion substrate by the inkjet method, it is necessary to keep the viscosity of the ink composition containing the luminescent nanocrystal particles within a certain range, and there is a problem that increasing the concentration of the luminescent nanocrystal particles and the light-scattering particles also increases the viscosity of the ink composition.
[0007] Therefore, an object of the present invention is to provide an ink composition that has a viscosity suitable for forming a pixel portion and that causes little leakage of blue light from a green pixel portion. [Means for solving the problem]
[0008] One aspect of the present invention is an ink composition containing luminescent nanocrystalline particles, a photopolymerizable compound and / or a thermosetting resin, and light-scattering particles, The present invention relates to an ink composition in which at least a portion of the luminescent nanocrystal particles absorb light in the wavelength range of 420 to 480 nm, have an emission peak in the range of 500 to 560 nm, and contain Ag, In, Ga, and S as constituent elements.
[0009] Since the ink composition of the present invention adopts the above-mentioned configuration, it is possible to effectively reduce blue light leakage from green pixel areas without increasing the concentration of luminescent nanocrystalline particles, and it is possible to keep the viscosity of the inkjet ink within a range suitable for forming pixel areas.
[0010] The ink composition may have a viscosity at 25° C. of 30 mPa·s or less.
[0011] When a light conversion layer having a thickness of 15 μm is formed using the ink composition, the leakage rate of blue light may be 10% or less.
[0012] One aspect of the present invention relates to a light conversion layer comprising a plurality of pixel portions and a light-shielding portion provided between the plurality of pixel portions, the plurality of pixel portions having light-emitting pixel portions including a cured product of the ink composition described above.
[0013] One aspect of the present invention relates to a color filter including the above-mentioned light conversion layer. Effect of the Invention
[0014] According to the present invention, it is possible to provide an ink composition that has a viscosity suitable for forming a pixel portion as an inkjet ink while reducing the leakage of blue light from a green pixel portion, as well as a light conversion layer and a color filter that use the inkjet ink. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view of a color filter according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail.
[0017] <Ink composition> The ink composition of one embodiment contains luminescent nanocrystalline particles, a photopolymerizable compound and / or a thermosetting resin, and light-scattering particles. This ink composition is an ink composition for color filters used for forming pixel portions of a color filter by an inkjet method.
[0018] Since the ink composition of the present embodiment is used for forming a color filter pixel portion by an inkjet system, it is possible to form a color filter pixel portion (light conversion layer) by simply using the ink composition in the required amount in the required area, without wasting relatively expensive materials such as luminescent nanocrystal particles and solvents.
[0019] [Luminescent nanocrystal particles] Luminescent nanocrystalline particles are nano-sized crystals that absorb excitation light and emit fluorescence or phosphorescence, and are, for example, crystals whose maximum particle size measured by a transmission electron microscope or a scanning electron microscope is 100 nm or less.
[0020] The luminescent nanocrystal particles can, for example, absorb light of a predetermined wavelength and emit light (fluorescence or phosphorescence) of a wavelength different from the absorbed wavelength. The luminescent nanocrystal particles may be red-luminescent nanocrystal particles (red-luminescent nanocrystal particles) that emit light (red light) having a peak emission wavelength in the range of 605 to 665 nm, green-luminescent nanocrystal particles (green-luminescent nanocrystal particles) that emit light (green light) having a peak emission wavelength in the range of 500 to 560 nm, or blue-luminescent nanocrystal particles (blue-luminescent nanocrystal particles) that emit light (blue light) having a peak emission wavelength in the range of 420 to 480 nm.
[0021] In this embodiment, it is preferable that at least a portion of the luminescent nanocrystal particles contained in the ink composition that forms green pixels are luminescent nanocrystal particles that contain Ag, In, Ga and S as constituent elements, absorb light with a wavelength in the range of 420 to 480 nm, and emit green light with an emission peak in the range of 500 to 560 nm.
[0022] The light absorbed by the luminescent nanocrystalline particles may be, for example, light having a wavelength in the range of 400 nm or more and less than 500 nm (particularly, light having a wavelength in the range of 420 to 480 nm) (blue light) or light having a wavelength in the range of 200 nm to 400 nm (ultraviolet light). The emission peak wavelength of the luminescent nanocrystalline particles can be confirmed, for example, in a fluorescence spectrum or phosphorescence spectrum measured using a spectrofluorometer.
[0023] The red light-emitting nanocrystalline particles preferably have an emission peak wavelength of 665nm or less, 663nm or less, 660nm or less, 658nm or less, 655nm or less, 653nm or less, 651nm or less, 650nm or less, 647nm or less, 645nm or less, 643nm or less, 640nm or less, 637nm or less, 635nm or less, 632nm or less, or 630nm or less, and preferably have an emission peak wavelength of 628nm or more, 625nm or more, 623nm or more, 620nm or more, 615nm or more, 610nm or more, 607nm or more, or 605nm or more. These upper and lower limit values can be arbitrarily combined. In the following similar descriptions, the upper and lower limit values individually described can be arbitrarily combined.
[0024] The green light-emitting nanocrystalline particles preferably have an emission peak wavelength of 560 nm or less, 557 nm or less, 555 nm or less, 550 nm or less, 547 nm or less, 545 nm or less, 543 nm or less, 540 nm or less, 537 nm or less, 535 nm or less, 532 nm or less, or 530 nm or less, and preferably have an emission peak wavelength of 528 nm or more, 525 nm or more, 523 nm or more, 520 nm or more, 515 nm or more, 510 nm or more, 507 nm or more, 505 nm or more, 503 nm or more, or 500 nm or more.
[0025] The blue-light-emitting nanocrystalline particles preferably have an emission peak wavelength of 480 nm or less, 477 nm or less, 475 nm or less, 470 nm or less, 467 nm or less, 465 nm or less, 463 nm or less, 460 nm or less, 457 nm or less, 455 nm or less, 452 nm or less, or 450 nm or less, and preferably have an emission peak wavelength of 450 nm or more, 445 nm or more, 440 nm or more, 435 nm or more, 430 nm or more, 428 nm or more, 425 nm or more, 422 nm or more, or 420 nm or more.
[0026] According to the solution of the Schrodinger wave equation of the well-well potential model, the wavelength (emission color) of light emitted by a luminescent nanocrystal particle depends on the size (e.g., particle diameter) of the luminescent nanocrystal particle, but also on the energy gap of the luminescent nanocrystal particle. Therefore, the emission color can be selected by changing the constituent material and size of the luminescent nanocrystal particle used.
[0027] The luminescent nanocrystal particles may be luminescent nanocrystal particles (luminescent semiconductor nanocrystal particles) containing a semiconductor material. Examples of the luminescent semiconductor nanocrystal particles include quantum dots and quantum rods. Among these, quantum dots are preferred from the viewpoints of easy control of the emission spectrum, reduced production costs, and improved mass productivity while ensuring reliability.
[0028] The luminescent semiconductor nanocrystal particle may be composed of only a core containing a first semiconductor material, or may have a core containing the first semiconductor material and a shell containing a second semiconductor material different from the first semiconductor material and covering at least a part of the core. In other words, the structure of the luminescent semiconductor nanocrystal particle may be a structure consisting of only a core (core structure), or a structure consisting of a core and a shell (core / shell structure). The luminescent semiconductor nanocrystal particle may further have a shell (second shell) containing a third semiconductor material different from the first and second semiconductor materials and covering at least a part of the core, in addition to the shell (first shell) containing the second semiconductor material. In other words, the structure of the luminescent semiconductor nanocrystal particle may be a structure consisting of a core, a first shell, and a second shell (core / shell / shell structure). Each of the core and the shell may be a mixed crystal containing two or more kinds of semiconductor materials (for example, CdSe+CdS, CIS+ZnS, etc.).
[0029] In this embodiment, the constituent elements of the semiconductor material preferably include Ag, In, Ga, and S. The composition ratio of Ag, In, Ga, and S may be in any range. Here, Ag is elemental silver, In is elemental indium, Ga is elemental gallium, and S is elemental sulfur. In addition, the luminescent nanocrystal particles containing Ag, In, Ga and S may be composed of only the core of the present semiconductor material, or the core / shell may be composed of the present semiconductor material. Similarly, in the case of a multi-layer structure such as core / shell / shell, a part of the structure may be composed of the present semiconductor material, or the entire structure may be composed of the present semiconductor material. In the case of a plurality of layers being composed of the present semiconductor material, the composition ratios of Ag, In, Ga and S in each layer may be the same or different. However, from the viewpoint of emission intensity and emission peak, it is preferable that the semiconductor material of the core is composed of the present semiconductor material. In addition, in the case of a part or the entire shell being composed of a semiconductor material other than the present semiconductor material, it is preferable that the semiconductor material contains at least one semiconductor material selected from the group consisting of II-VI group semiconductors, III-V group semiconductors, I-III-VI group semiconductors, IV group semiconductors and I-II-IV-VI group semiconductors. The luminescent nanocrystalline particles preferably contain, as a semiconductor material, at least one semiconductor material selected from the group consisting of II-VI semiconductors, III-V semiconductors, I-III-VI semiconductors, Group IV semiconductors, and I-II-IV-VI semiconductors.
[0030] Specific semiconductor materials include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, CdHgZnTe , CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe; GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, Al PAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb;SnS, SnSe, SnTe, PbS, PbSe , PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; Si, Ge, SiC, SiGe, AgInSe2, CuGaSe2, CuInS2, CuGaS2, CuInSe2, AgInS2, AgGaSe2, AgGaS2, C, Si and Ge. From the viewpoints of easily controlling the emission spectrum and ensuring reliability, reducing production costs, and improving mass productivity, it is preferable that the luminescent semiconductor nanocrystal particles contain at least one selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, InP, InAs, InSb, GaP, GaAs, GaSb, AgInS2, AgInSe2, AgInTe2, AgGaS2, AgGaSe2, AgGaTe2, CuInS2, CuInSe2, CuInTe2, CuGaS2, CuGaSe2, CuGaTe2, Si, C, Ge, and Cu2ZnSnS4.
[0031] Furthermore, when formulating the ink composition, the luminescent nanocrystal particles may be used in combination with luminescent nanocrystals that do not contain a semiconductor material composed of Ag, In, Ga, and S. In that case, any of the semiconductor materials described below may be used as the semiconductor material.
[0032] Examples of red-emitting semiconductor nanocrystal particles include CdSe nanocrystal particles, nanocrystal particles having a core / shell structure in which the shell portion is CdS and the inner core portion is CdSe, nanocrystal particles having a core / shell structure in which the shell portion is CdS and the inner core portion is ZnSe, nanocrystal particles of a mixed crystal of CdSe and ZnS, InP nanocrystal particles, nanocrystal particles having a core / shell structure in which the shell portion is ZnS and the inner core portion is InP, and nanocrystal particles having a core / shell structure. Examples of such nanocrystal particles include nanocrystal particles whose shell portion is a mixed crystal of ZnS and ZnSe and whose inner core portion is InP, nanocrystal particles of a mixed crystal of CdSe and CdS, nanocrystal particles of a mixed crystal of ZnSe and CdS, nanocrystal particles with a core / shell / shell structure in which the first shell portion is ZnSe, the second shell portion is ZnS, and the inner core portion is InP, and nanocrystal particles with a core / shell / shell structure in which the first shell portion is a mixed crystal of ZnS and ZnSe, the second shell portion is ZnS, and the inner core portion is InP.
[0033] Examples of green-emitting semiconductor nanocrystal particles include CdSe nanocrystal particles, nanocrystal particles of a mixed crystal of CdSe and ZnS, nanocrystal particles having a core / shell structure in which the shell portion is ZnS and the inner core portion is InP, nanocrystal particles having a core / shell structure in which the shell portion is a mixed crystal of ZnS and ZnSe and the inner core portion is InP, nanocrystal particles having a core / shell / shell structure in which the first shell portion is ZnSe, the second shell portion is ZnS, and the inner core portion is InP, and nanocrystal particles having a core / shell / shell structure in which the first shell portion is a mixed crystal of ZnS and ZnSe, the second shell portion is ZnS, and the inner core portion is InP.
[0034] Examples of blue-emitting semiconductor nanocrystal particles include ZnSe nanocrystal particles, ZnS nanocrystal particles, nanocrystal particles having a core / shell structure in which the shell part is ZnSe and the inner core part is ZnS, CdS nanocrystal particles, nanocrystal particles having a core / shell structure in which the shell part is ZnS and the inner core part is InP, nanocrystal particles having a core / shell structure in which the shell part is a mixed crystal of ZnS and ZnSe and the inner core part is InP, nanocrystal particles having a core / shell / shell structure in which a first shell part is ZnSe, a second shell part is ZnS, and an inner core part is InP, nanocrystal particles having a core / shell / shell structure in which a first shell part is a mixed crystal of ZnS and ZnSe, a second shell part is ZnS, and an inner core part is InP, and the like.
[0035] By changing the average particle diameter of semiconductor nanocrystal particles with the same chemical composition, the color to be emitted from the particles can be changed to red or green. In addition, it is preferable to use semiconductor nanocrystal particles that have as little adverse effect on the human body as possible. When using semiconductor nanocrystal particles containing cadmium, selenium, etc. as luminescent nanocrystal particles, it is preferable to select semiconductor nanocrystal particles that contain as little of the above elements (cadmium, selenium, etc.) as possible and use them alone, or to use them in combination with other luminescent nanocrystal particles so that the amount of the above elements is as small as possible.
[0036] The shape of the luminescent nanocrystal particles is not particularly limited, and may be any geometric shape or any irregular shape. The shape of the luminescent nanocrystal particles may be, for example, spherical, ellipsoidal, pyramidal, discoid, branched, net-like, rod-like, etc. However, it is preferable to use particles with little directional particle shape (for example, spherical, regular tetrahedral, etc.) as the luminescent nanocrystal particles, in order to further improve the uniformity and flowability of the ink composition.
[0037] The average particle size (volume average size) of the luminescent nanocrystal particles may be 1 nm or more, 1.5 nm or more, or 2 nm or more from the viewpoint of easily obtaining light emission of a desired wavelength and excellent dispersibility and storage stability. From the viewpoint of easily obtaining a desired emission wavelength, it may be 40 nm or less, 30 nm or less, or 20 nm or less. The average particle size (volume average size) of the luminescent nanocrystal particles is obtained by measuring with a transmission electron microscope or a scanning electron microscope and calculating the volume average size.
[0038] The luminescent nanocrystal particles have an organic ligand on their surface from the viewpoint of dispersion stability. The organic ligand may be, for example, coordinated to the surface of the luminescent nanocrystal particles. In other words, the surface of the luminescent nanocrystal particles may be passivated by the organic ligand. In addition, when the ink composition further contains a polymer dispersant described later, the luminescent nanocrystal particles may have a polymer dispersant on their surface. In this embodiment, for example, the organic ligand may be removed from the luminescent nanocrystal particles having the above-mentioned organic ligand, and the organic ligand may be exchanged with the polymer dispersant to bond the polymer dispersant to the surface of the luminescent nanocrystal particles. However, from the viewpoint of dispersion stability when the ink composition is prepared, it is preferable that the polymer dispersant is mixed with the luminescent nanocrystal particles with the organic ligand still coordinated.
[0039] The organic ligand may contain a functional group (hereinafter also referred to as "affinity group") for ensuring affinity with photopolymerizable compounds, thermosetting resins, organic solvents, etc. The affinity group may be a substituted or unsubstituted aliphatic hydrocarbon group. The aliphatic hydrocarbon group may be a straight chain type or may have a branched structure. The aliphatic hydrocarbon group may or may not have an unsaturated bond. The substituted aliphatic hydrocarbon may be a group in which some carbon atoms of the aliphatic hydrocarbon group are substituted with oxygen atoms. The substituted aliphatic hydrocarbon group may contain, for example, a (poly)oxyalkylene group.
[0040] The organic ligand preferably contains a polyoxyalkylene group. The polyoxyalkylene group is a divalent group formed by linking two or more alkylene groups with ether bonds, and has a plurality of oxyalkylene structures (oxyalkylene groups). The plurality of alkylene groups constituting the polyoxyalkylene group may be the same or different from each other. The alkylene group may be linear or may have a branched structure. In addition, the alkylene group may or may not have an unsaturated bond.
[0041] The number of carbon atoms in the alkylene group may be, for example, 1 or more, 2 or more, or 3 or more, and 5 or less, 4 or less, or 3 or less. The alkylene group is preferably an ethylene group, a propylene group, or a butylene group. That is, the polyoxyalkylene group preferably has at least one selected from the group consisting of an oxyalkylene structure having an ethylene group (oxyethylene structure), an oxyalkylene structure having a propylene group (oxypropylene structure), and an oxyalkylene structure having a butylene group (oxybutylene structure).
[0042] The polyoxyalkylene group preferably has an oxyalkylene structure represented by the following formula (1).
[0043] [ka]
[0044] In formula (1), R 1 and R 2 R each independently represents a hydrogen atom, a methyl group, or an ethyl group, and * represents a bond. 1 and R 2 When one of R is a methyl group or an ethyl group, the other is preferably a hydrogen atom. 1 and R 2 is preferably a hydrogen atom or a methyl group. 1 and R 2 an oxyethylene structure in which R is a hydrogen atom, or 1 and R 2 An oxypropylene structure in which one of the groups is a methyl group and the other is a hydrogen atom is more preferred.
[0045] When the polyoxyalkylene group has a plurality of structures represented by formula (1), a plurality of R 1 may be the same or different, and multiple R 2 may be the same or different.
[0046] The degree of polymerization of the polyoxyalkylene group may be, for example, 2 or more, 4 or more, or 6 or more, and may be 40 or less, 30 or less, or 20 or less. Here, the degree of polymerization of the polyoxyalkylene group means the number of repetitions of the oxyalkylene structure (the number of alkylene groups linked by ether bonds).
[0047] When the polyoxyalkylene group contains a repeating oxyethylene structure, the number of repeating oxyethylene structures may be 2 or more, 4 or more, or 6 or more, and may be 40 or less, 30 or less, or 20 or less.
[0048] When the polyoxyalkylene group contains a repeat of an oxypropylene structure, the number of repeats of the oxypropylene structure may be 2 or more, 4 or more, or 6 or more, and may be 40 or less, 30 or less, or 20 or less.
[0049] The polyoxyalkylene group may be contained in the main chain of the organic ligand, where the main chain refers to the longest molecular chain among the molecular chains constituting the organic ligand.
[0050] The organic ligand preferably contains a functional group capable of binding to the luminescent nanocrystal particles (a functional group for ensuring adsorption to the luminescent nanocrystal particles). Examples of the functional group capable of binding to the luminescent nanocrystal particles include a hydroxyl group, an amino group, a carboxyl group, a thiol group, a phosphoric acid group, a phosphonic acid group, a phosphine group, a phosphine oxide group, and an alkoxysilyl group. These functional groups may be bound to the luminescent nanocrystal particles by a coordinate bond or the like.
[0051] The number of functional groups in the organic ligand capable of bonding to the luminescent nanocrystal particles may be 1 to 3, may be 1 to 2, or may be 1. At least one of the functional groups in the organic ligand on the surface of the luminescent nanocrystal particles capable of bonding to the luminescent nanocrystal particles may be a functional group bonded to the luminescent nanocrystal particles. In addition, when the organic ligand contains a plurality of functional groups capable of bonding to the luminescent nanocrystal particles, some of the plurality of functional groups may not be bonded to the luminescent nanocrystal particles.
[0052] The functional group capable of bonding with the luminescent nanocrystalline particle may be present at at least one end of the main chain of the organic ligand, i.e., the organic ligand may include a functional group at at least one end of the main chain that is capable of bonding with the luminescent nanocrystalline particle.
[0053] The organic ligand may have a hydrogen-bonding group. Here, the hydrogen-bonding functional group means a group having a hydrogen atom capable of forming a hydrogen bond with a carbonyl group or the like. The hydrogen-bonding group may be a group capable of bonding with a luminescent nanocrystal particle. The organic ligand present on the surface of the luminescent nanocrystal particle preferably has a hydrogen-bonding group that is not bonded to the luminescent nanocrystal particle. Examples of the hydrogen-bonding group include monovalent groups such as a hydroxyl group, an amino group, a carboxyl group, and a thiol group, and divalent groups such as an amide group (-NHCO-).
[0054] The organic ligand may have at least one first functional group capable of binding to the luminescent nanocrystalline particle at one end of the main chain, and may have at the other end of the main chain a second functional group different from the first functional group. The first functional group may be the same as the functional group capable of binding to the luminescent nanocrystalline particle described above. The number of first functional groups may be one or more, may be two or more, or may be two. The second functional group may be the same as the functional group capable of binding to the luminescent nanocrystalline particle described above, or may be another group different from the functional group. The other group may be, for example, an alkyl group, a cycloalkyl group, or an aryl group. The number of second functional groups may be one or more, or may be one.
[0055] The main chain may have, for example, a substituted or unsubstituted hydrocarbon group in addition to the polyoxyalkylene group. The number of carbon atoms in the substituted or unsubstituted hydrocarbon group may be, for example, 1 to 10. In the substituted hydrocarbon group, a part of the carbon atoms may be substituted with a heteroatom such as a sulfur atom or a nitrogen atom, a carbonyl group, or the like.
[0056] In one embodiment, the organic ligand may be a compound represented by the following formula (1-1):
[0057] [ka]
[0058] In formula (1-1), p represents an integer of 0 to 50, and q represents an integer of 0 to 50. At least one of p and q is preferably 1 or greater, and both of p and q are more preferably 1 or greater.
[0059] In one embodiment, the organic ligand may be an organic ligand represented by the following formula (1-2):
[0060] [ka]
[0061] [In formula (1-2), r represents an integer of 1 to 50.]
[0062] In the organic ligand represented by formula (1-2), r may be 1 to 20, 3 to 15, 5 to 10, or 7.
[0063] The organic ligand may be a ligand having two or more functional groups capable of binding to the luminescent nanocrystalline particles, that is, in one embodiment, the organic ligand may be a compound represented by the following formula (1-3):
[0064] [ka]
[0065] In formula (1-3), A 1 and A 2 each independently represents a monovalent group that may contain a functional group capable of bonding to the above-mentioned luminescent nanocrystalline particles; R represents a hydrogen atom, a methyl group, or an ethyl group; L 1 and L 2Each independently represents a substituted or unsubstituted alkylene group, and s represents an integer of 0 or more. 1 and A 2 At least one of A contains a functional group capable of binding to the luminescent nanocrystalline particles described above, 1 and A 2 The total number of functional groups capable of binding to the luminescent nanocrystal particles in is 2 or more. 1 Or A 2 is a group that does not contain a functional group capable of bonding to a luminescent nanocrystalline particle, 1 Or A 2 may be, for example, a hydrogen atom.
[0066] A 1 and A 2 The number of functional groups capable of bonding to the luminescent nanocrystalline particles in the monovalent group represented by the formula (I) may be 1 or 2 or more, may be 4 or less, or may be 2. The functional group capable of bonding to the luminescent nanocrystalline particles is preferably at least one selected from the group consisting of a hydroxyl group and a carboxyl group.
[0067] In one embodiment, A 1 The number of functional groups capable of bonding to the luminescent nanocrystal particles in the monovalent group represented by 2 It is preferable that the number of functional groups capable of bonding to the luminescent nanocrystal particles in the monovalent group represented by the formula: 1 In the monovalent group represented by the formula: 2 It is more preferable that the functional group capable of bonding to the luminescent nanocrystalline particle in the monovalent group represented by the formula: is a hydroxyl group.
[0068] In another embodiment, A 1 The number of functional groups capable of bonding to the luminescent nanocrystal particles in the monovalent group represented by 2 is a hydrogen atom (i.e., A 2 It is preferable that the number of functional groups capable of bonding to the luminescent nanocrystal particles in the monovalent group represented by1 It is more preferable that the two functional groups capable of bonding to the luminescent nanocrystal particles in the monovalent group represented by the formula:
[0069] The number of carbon atoms in the alkylene group represented by L may be, for example, 1 to 10. In the alkylene group represented by L, a part of the carbon atoms (methylene group) may be substituted with a heteroatom. When L is a substituted alkylene group, in the alkylene group, a part of the carbon atoms (methylene group) is preferably substituted with at least one heteroatom selected from the group consisting of an oxygen atom, a sulfur atom, and a nitrogen atom, more preferably substituted with a sulfur atom. s may be, for example, an integer of 1 or more, 3 or more, or 5 or more, and may be an integer of 100 or less, 20 or less, or 10 or less.
[0070] The organic ligand is preferably a compound represented by the following formula (1-4).
[0071] [ka]
[0072] In formula (1-4), p and q are each independently an integer of 0 or more, r is an integer of 1 or more, and A 1 , A 2 and s is A in formula (1-3). 1 , A 2 and s, respectively, provided that at least one of p and q is an integer of 1 or greater.
[0073] p may be an integer of 3 or less, 2 or less, or 1 or less, or may be 0. q may be an integer of 1 or more, 2 or more, or 3 or more, or may be an integer of 5 or less, 4 or less, or 3 or less, or may be 3. r may be an integer of 4 or less, 3 or less, or 2 or less, or may be 1.
[0074] The organic ligand is more preferably a compound represented by the following formula (1-5) or (1-6).
[0075] [ka]
[0076] In formulas (1-5) and (1-6), s has the same meaning as s in formula (1-3).
[0077] Examples of organic ligands that contain functional groups capable of binding to luminescent nanocrystalline particles include TOP (trioctylphosphine), TOPO (trioctylphosphine oxide), lauric acid, oleic acid, oleylamine, octylamine, trioctylamine, hexadecylamine, octanethiol, dodecanethiol, hexylphosphonic acid (HPA), tetradecylphosphonic acid (TDPA), and octylphosphinic acid (OPA).
[0078] From the viewpoint of providing an ink composition with a viscosity more suitable for forming pixel portions, the weight average molecular weight of the organic ligand is 1000 or less, and may be 900 or less, 800 or less, 700 or less, or 600 or less, or may be 250 or more, 300 or more, 400 or more, 450 or more, 500 or more, or 550 or more. In this specification, the weight average molecular weight refers to the polystyrene-equivalent weight average molecular weight measured by GPC (gel permeation chromatography).
[0079] The luminescent nanocrystal particles may be dispersed in a colloidal form in an organic solvent, a photopolymerizable compound, or the like. The surface of the luminescent nanocrystal particles dispersed in the organic solvent is preferably passivated by the organic ligand described above. Examples of the organic solvent include cyclohexane, hexane, heptane, chloroform, toluene, octane, chlorobenzene, tetralin, diphenyl ether, propylene glycol monomethyl ether acetate, butyl carbitol acetate, 1,4-butanediol diacetate, and mixtures thereof.
[0080] The luminescent nanocrystal particles may be commercially available products, such as indium phosphide / zinc sulfide, D-dot, and CuInS / ZnS from NN-Labs, and InP / ZnS from Aldrich.
[0081] The content of the luminescent nanocrystal particles having Ag, In, Ga and S is preferably more than 5 parts by mass, more preferably 7 parts by mass or more, and even more preferably 10 parts by mass or more, based on 100 parts by mass of the total content (total content of non-volatile contents) of the luminescent nanocrystal particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of blue light leakage. When the content of the luminescent nanocrystal particles is more than 10 parts by mass, the ink composition has excellent absorptivity of blue light, and therefore such an ink composition is suitably used for color filters. The content of the luminescent nanocrystal particles having Ag, In, Ga and S is preferably 60 parts by mass or less, may be 50 parts by mass or less, may be 40 parts by mass or less, or may be 35 parts by mass or less, based on 100 parts by mass of the total content (total content of non-volatile contents) of the luminescent nanocrystal particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of excellent ejection stability and curability. The content of the luminescent nanocrystal particles may be more than 10 parts by mass and not more than 60 parts by mass, 13 to 60 parts by mass, 15 to 60 parts by mass, more than 10 parts by mass and not more than 50 parts by mass, more than 10 parts by mass and not more than 40 parts by mass, or more than 10 parts by mass and not more than 35 parts by mass, relative to 100 parts by mass of the total content (total content of non-volatile contents) of the luminescent nanocrystal particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition. In addition, the luminescent nanocrystal particles may be a mixture of luminescent nanocrystal particles having Ag, In, Ga, and S and other luminescent nanocrystal particles.
[0082] The total content (total content of non-volatile content) of the luminescent nanocrystal particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition is 41% by mass or more, 45% by mass or more, 50% by mass or more, 55% by mass or more, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more, or may be 100% by mass. When the total content (total content of non-volatile content) of the luminescent nanocrystal particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition is 70% by mass or more based on the total mass of the ink composition, it is preferably used as an ink composition that does not contain a solvent.
[0083] When the ink composition contains a photopolymerizable compound but does not contain a thermosetting resin, the total content of the nonvolatile components is the total content of the luminescent nanocrystalline particles, the organic ligand, the photopolymerizable compound, and the light scattering particles. When the ink composition contains a thermosetting resin but does not contain a photopolymerizable compound, the total content of the nonvolatile components is the total content of the luminescent nanocrystalline particles, the organic ligand, the thermosetting resin, and the light scattering particles.
[0084] The ink composition may contain two or more of red luminescent nanocrystal particles, green luminescent nanocrystal particles, and blue luminescent nanocrystal particles as the luminescent nanocrystal particles, but preferably contains only one of these particles. When the ink composition contains red luminescent nanocrystal particles, the content of the green luminescent nanocrystal particles and the content of the blue luminescent nanocrystal particles are preferably 10% by mass or less, more preferably 0% by mass, based on the total mass of the luminescent nanocrystal particles. When the ink composition contains green luminescent nanocrystal particles, the content of the red luminescent nanocrystal particles and the content of the blue luminescent nanocrystal particles are preferably 10% by mass or less, more preferably 0% by mass, based on the total mass of the luminescent nanocrystal particles.
[0085] The total content of the luminescent nanocrystal particles having Ag, In, Ga, and S, and the organic ligand, relative to 100 parts by mass of the total content of the luminescent nanocrystal particles, the organic ligand, the photopolymerizable compound, the thermosetting resin, and the light-scattering particles in the ink composition, is 5 parts by mass or more, and may be 10 parts by mass or more, 15 parts by mass or more, 21 parts by mass or more, 25 parts by mass or more, 27 parts by mass or more, 30 parts by mass or more, 35 parts by mass or more, 40 parts by mass or more, 45 parts by mass or more, or 50 parts by mass or more, and may be 70 parts by mass or less, 65 parts by mass or less, 60 parts by mass or less, or 55 parts by mass, 50 parts by mass, or 45 parts by mass or less.
[0086] The content of the organic ligand is 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, 30 parts by mass or more, or 32 parts by mass or more, and may be 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or less, or 38 parts by mass or less, relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles and the organic ligand, from the viewpoint of suppressing thickening of the ink composition due to exposure to the atmosphere. When the content of the organic ligand is 50 parts by mass or less relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles and the organic ligand, the content of the luminescent nanocrystalline particles in the ink composition can be relatively high, which is preferable. In this specification, the content of the organic ligand relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles and the organic ligand is defined as the organic ratio (ratio of organic compounds) obtained by measuring a mixture composed of the luminescent nanocrystalline particles and the organic ligand by TG-DTA. The mixture composed of the luminescent nanocrystalline particles and the organic ligand can be obtained by adding a poor solvent for the mixture to the ink composition, allowing the mixture to settle, and then drying.
[0087] [Photopolymerizable compound] The photopolymerizable compound of the present embodiment is a compound that polymerizes by irradiation with light, and is, for example, a photoradical polymerizable compound or a photocationic polymerizable compound. The photopolymerizable compound may be a photopolymerizable monomer or oligomer. These are used together with a photopolymerization initiator. The photoradical polymerizable compound is used together with a photoradical polymerization initiator, and the photocationic polymerizable compound is used together with a photocationic polymerization initiator. In other words, the ink composition may contain a photopolymerizable component including a photopolymerizable compound and a photopolymerization initiator, may contain a photoradical polymerizable component including a photoradical polymerizable compound and a photoradical polymerization initiator, or may contain a photocationic polymerizable component including a photocationic polymerizable compound and a photocationic polymerization initiator. A photoradical polymerizable compound and a photocationic polymerizable compound may be used in combination, a compound having photoradical polymerizability and photocationic polymerizability may be used, or a photoradical polymerization initiator and a photocationic polymerization initiator may be used in combination. The photopolymerizable compound may be used alone or in combination of two or more types.
[0088] Examples of photoradical polymerizable compounds include monomers having an ethylenically unsaturated group (hereinafter also referred to as "ethylenically unsaturated monomers") and monomers having an isocyanate group. Here, the ethylenically unsaturated monomer means a monomer having an ethylenically unsaturated bond (carbon-carbon double bond). Examples of the ethylenically unsaturated monomer include monomers having an ethylenically unsaturated group such as a vinyl group, a vinylene group, or a vinylidene group. Monomers having these groups are sometimes referred to as "vinyl monomers".
[0089] The number of ethylenically unsaturated bonds in the ethylenically unsaturated monomer (for example, the number of ethylenically unsaturated groups) is, for example, 1 to 3. One type of ethylenically unsaturated monomer may be used alone, or a combination of multiple types may be used. From the viewpoint of easily achieving both excellent discharge stability and excellent curability, and from the viewpoint of further improving external quantum efficiency, the photopolymerizable compound may contain a monomer having one or two ethylenically unsaturated groups and a monomer having two or three ethylenically unsaturated groups. That is, the ethylenically unsaturated monomer may contain at least one combination selected from the group consisting of a monofunctional monomer and a bifunctional monomer, a monofunctional monomer and a trifunctional monomer, a bifunctional monomer and a bifunctional monomer, and a bifunctional monomer and a trifunctional monomer. In this embodiment, it is preferable that the photopolymerizable compound contains two or more types of monomers having two ethylenically unsaturated bonds.
[0090] Examples of the ethylenically unsaturated group include a vinyl group, a vinylene group, a vinylidene group, and a (meth)acryloyl group. In this specification, the term "(meth)acryloyl group" means an "acryloyl group" and the corresponding "methacryloyl group". The same applies to the expressions "(meth)acrylate" and "(meth)acrylamide".
[0091] Examples of monofunctional monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, nonylphenoxyethyl (meth)acrylate, glycidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and ethoxyethoxyethyl (meth)acrylate. , isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, benzyl (meth)acrylate, phenylbenzyl (meth)acrylate, mono(2-acryloyloxyethyl) succinate, mono(2-methacryloyloxyethyl) succinate, N-[2-(acryloyloxy)ethyl]phthalimide, N-[2-(acryloyloxy)ethyl]tetrahydrophthalimide, 4-hydroxybutyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl acrylate, etc. Among these, ethoxyethoxyethyl (meth)acrylate is preferably used.
[0092] Specific examples of monomers having two ethylenically unsaturated groups (bifunctional monomers) include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol hydroxypivalic acid ester diacrylate, tris(2-hydroxyethyl)isocyanate Examples of the di(meth)acrylate include a di(meth)acrylate in which two hydroxyl groups of nurate are substituted with (meth)acryloyloxy groups, a diol obtained by adding 4 moles or more of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol, and two hydroxyl groups of the diol obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A are substituted with (meth)acryloyloxy groups, a di(meth)acrylate in which two hydroxyl groups of a triol obtained by adding 3 moles or more of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane are substituted with (meth)acryloyloxy groups, and a di(meth)acrylate in which two hydroxyl groups of a diol obtained by adding 4 moles or more of ethylene oxide or propylene oxide to 1 mole of bisphenol A are substituted with (meth)acryloyloxy groups. Of these, dipropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, and 1,6-hexanediol diacrylate are preferably used.
[0093] Specific examples of monomers having three ethylenically unsaturated groups (trifunctional monomers) include glycerin tri(meth)acrylate, trimethylolethane tri(meth)acrylate, etc. Among these, glycerin tri(meth)acrylate is preferably used.
[0094] Examples of the photocationically polymerizable compound include an epoxy compound, an oxetane compound, and a vinyl ether compound.
[0095] Examples of the epoxy compound include aliphatic epoxy compounds such as bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, phenol novolac type epoxy compounds, trimethylolpropane polyglycidyl ether and neopentyl glycol diglycidyl ether, and alicyclic epoxy compounds such as 1,2-epoxy-4-vinylcyclohexane and 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4.1.0]heptane.
[0096] It is also possible to use commercially available epoxy compounds, such as "Celloxide 2000", "Celloxide 3000", and "Celloxide 4000" manufactured by Daicel Chemical Industries, Ltd.
[0097] Examples of the cationically polymerizable oxetane compound include 2-ethylhexyl oxetane, 3-hydroxymethyl-3-methyl oxetane, 3-hydroxymethyl-3-ethyl oxetane, 3-hydroxymethyl-3-propyl oxetane, 3-hydroxymethyl-3-normal butyl oxetane, 3-hydroxymethyl-3-phenyl oxetane, 3-hydroxymethyl-3-benzyl oxetane, 3-hydroxyethyl-3-methyl oxetane, 3-hydroxyethyl-3-ethyl oxetane, 3-hydroxyethyl-3-propyl oxetane, 3-hydroxyethyl-3-phenyl oxetane, 3-hydroxypropyl-3-methyl oxetane, 3-hydroxypropyl-3-ethyl oxetane, 3-hydroxypropyl-3-propyl oxetane, 3-hydroxypropyl-3-phenyl oxetane, and 3-hydroxybutyl-3-methyl oxetane.
[0098] It is also possible to use commercially available products as the oxetane compound. Examples of commercially available oxetane compounds include the Aron Oxetane series (such as "OXT-101", "OXT-212", "OXT-121", and "OXT-221") manufactured by Toagosei Co., Ltd.; "Celloxide 2021", "Celloxide 2021A", "Celloxide 2021P", "Celloxide 2080", "Celloxide 2081", "Celloxide 2083", "Celloxide 2085", "Celloxide 2086", "Celloxide 2087", "Celloxide 2088", "Celloxide 2089", "Celloxide 2090", "Celloxide 2091", "Celloxide 2092", "Celloxide 2093", "Celloxide 2094", "Celloxide 2095", "Celloxide 2096", "Celloxide 2097", "Celloxide 2098", "Celloxide 2099", "Celloxide 2090", "Celloxide 2091", "Celloxide 2092", "Celloxide 2093", "Celloxide 2094", "Celloxide 2095", "Celloxide 2095", "Celloxide 2096", "Celloxide 2097", "Celloxide 2098", "Celloxide 209 ... Epolead GT300, Epolead GT301, Epolead GT302, Epolead GT400, Epolead GT401 and Epolead GT403; Cyracure UVR-6105, Cyracure UVR-6107, Cyracure UVR-6110, Cyracure UVR-6128, ERL4289 and ERL4299 manufactured by Dow Chemical Japan Co., Ltd. can be used. In addition, known oxetane compounds (for example, oxetane compounds described in JP-A-2009-40830, etc.) can also be used.
[0099] Examples of the vinyl ether compound include 2-hydroxyethyl vinyl ether, triethylene glycol vinyl monoether, tetraethylene glycol divinyl ether, and trimethylolpropane trivinyl ether.
[0100] In addition, as the photopolymerizable compound in this embodiment, the photopolymerizable compounds described in paragraphs 0042 to 0049 of JP-A-2013-182215 can also be used.
[0101] The photopolymerizable compound may be alkali-insoluble from the viewpoint of easily obtaining a pixel portion (cured product of the ink composition) having excellent reliability. In this specification, the photopolymerizable compound being alkali-insoluble means that the amount of the photopolymerizable compound dissolved in a 1% by mass aqueous potassium hydroxide solution at 25°C is 30% by mass or less based on the total mass of the photopolymerizable compound. The above-mentioned amount of the photopolymerizable compound dissolved is preferably 10% by mass or less, more preferably 3% by mass or less.
[0102] The content of the photopolymerizable compound may be 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more relative to the total content of 100 parts by mass of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of easily obtaining an appropriate viscosity as an ink composition, from the viewpoint of good curability of the ink composition, and from the viewpoint of improving the solvent resistance and abrasion resistance of the pixel portion (cured product of the ink composition). The content of the photopolymerizable compound may be 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less relative to the total content of 100 parts by mass of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of easily obtaining an appropriate viscosity as an ink composition and from the viewpoint of obtaining better optical properties (for example, the effect of suppressing the decrease in external quantum efficiency).
[0103] [Photopolymerization initiator] The photopolymerization initiator is, for example, a photoradical polymerization initiator. As the photoradical polymerization initiator, a molecular cleavage type or hydrogen abstraction type photoradical polymerization initiator is preferable.
[0104] As the molecular cleavage type photoradical polymerization initiator, benzoin isobutyl ether, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, etc. are preferably used. As other molecular cleavage type photoradical polymerization initiators, 1-hydroxycyclohexyl phenyl ketone, benzoin ethyl ether, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one may be used in combination.
[0105] Examples of the hydrogen abstraction type photoradical polymerization initiator include benzophenone, 4-phenylbenzophenone, isophthalphenone, 4-benzoyl-4'-methyl-diphenyl sulfide, etc. A molecular cleavage type photoradical polymerization initiator and a hydrogen abstraction type photoradical polymerization initiator may be used in combination.
[0106] Commercially available products can also be used as the photocationic polymerization initiator. Examples of commercially available products include sulfonium salt-based photocationic polymerization initiators such as "CPI-100P" manufactured by San-Apro Co., Ltd., acylphosphine oxide compounds such as "Lucirin TPO" manufactured by BASF Co., Ltd., and "Irgacure 907", "Irgacure 819", "Irgacure 379EG", "Irgacure 184" and "Irgacure PAG290" manufactured by BASF Co., Ltd.
[0107] The content of the photopolymerization initiator may be 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more relative to 100 parts by mass of the photopolymerizable compound from the viewpoint of the curability of the ink composition. The content of the photopolymerization initiator may be 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less relative to 100 parts by mass of the photopolymerizable compound from the viewpoint of the stability over time of the pixel portion (cured product of the ink composition).
[0108] [Thermosetting resin] In this embodiment, the thermosetting resin is a resin that crosslinks and hardens due to heat. The thermosetting resin is, for example, a resin that functions as a binder in the cured product. The thermosetting resin has a curable group. Examples of the curable group include an epoxy group, an oxetane group, an isocyanate group, an amino group, a carboxyl group, and a methylol group. From the viewpoint of excellent heat resistance and storage stability of the cured product of the ink composition, and excellent adhesion to the light-shielding part (e.g., black matrix) and the substrate, an epoxy group is preferable. The thermosetting resin may have one type of curable group, or may have two or more types of curable groups.
[0109] The thermosetting resins include resins having photoradical polymerizability (polymerized by irradiation with light when used together with a photoradical polymerization initiator) and resins having photocationic polymerizability (polymerized by irradiation with light when used together with a photocationic polymerization initiator). When the ink composition contains a thermosetting resin having photoradical polymerizability and a photoradical polymerization initiator, the thermosetting resin having photoradical polymerizability is classified as a photoradical polymerizable compound (photopolymerizable compound). When the ink composition contains a thermosetting resin having photocationic polymerizability and a photocationic polymerization initiator, the thermosetting resin having photocationic polymerizability is classified as a photocationic polymerizable compound (photopolymerizable compound).
[0110] The thermosetting resin may be a polymer (homopolymer) of a single monomer, or a copolymer of multiple types of monomers. The thermosetting resin may be any of a random copolymer, a block copolymer, and a graft copolymer.
[0111] As the thermosetting resin, a compound having two or more thermosetting groups in one molecule is used, and is usually used in combination with a curing agent. When using a thermosetting resin, a catalyst (curing accelerator) capable of accelerating the thermosetting reaction may be further added. In other words, the ink composition may contain a thermosetting component including a thermosetting resin (and a curing agent and a curing accelerator used as necessary). In addition to these, a polymer that does not have polymerization reactivity itself may be further used.
[0112] As a compound having two or more thermosetting groups in one molecule, for example, an epoxy resin having two or more epoxy groups in one molecule (hereinafter, also referred to as "multifunctional epoxy resin") may be used. "Epoxy resin" includes both monomeric epoxy resins and polymeric epoxy resins. The number of epoxy groups in one molecule of a multifunctional epoxy resin is preferably 2 to 50, more preferably 2 to 20. The epoxy group may be any structure having an oxirane ring structure, and may be, for example, a glycidyl group, an oxyethylene group, an epoxycyclohexyl group, or the like. As the epoxy resin, a known polyfunctional epoxy resin that can be cured by a carboxylic acid may be mentioned. Such epoxy resins are widely disclosed in, for example, "Epoxy Resin Handbook" edited by Shinbo Masaki, published by Nikkan Kogyo Shimbun (1987), and these can be used.
[0113] Examples of the thermosetting resin having an epoxy group (including a polyfunctional epoxy resin) include a polymer of a monomer having an oxirane ring structure, and a copolymer of a monomer having an oxirane ring structure and another monomer. Specific examples of the polyfunctional epoxy resin include polyglycidyl methacrylate, methyl methacrylate-glycidyl methacrylate copolymer, benzyl methacrylate-glycidyl methacrylate copolymer, n-butyl methacrylate-glycidyl methacrylate copolymer, 2-hydroxyethyl methacrylate-glycidyl methacrylate copolymer, (3-ethyl-3-oxetanyl)methyl methacrylate-glycidyl methacrylate copolymer, and styrene-glycidyl methacrylate. In addition, the compounds described in paragraphs 0044 to 0066 of JP 2014-56248 A can also be used as the thermosetting resin of this embodiment.
[0114] Examples of polyfunctional epoxy resins that can be used include bisphenol A type epoxy resins, bisphenol F type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol S type epoxy resins, diphenyl ether type epoxy resins, hydroquinone type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, fluorene type epoxy resins, phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, trishydroxyphenylmethane type epoxy resins, trifunctional type epoxy resins, tetraphenylolethane type epoxy resins, dicyclopentadiene phenol type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol A nucleus-containing polyol type epoxy resins, polypropylene glycol type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, glyoxal type epoxy resins, alicyclic type epoxy resins, and heterocyclic type epoxy resins.
[0115] More specifically, bisphenol A type epoxy resins such as the product name "Epicoat 828" (manufactured by Japan Epoxy Resins Co., Ltd.), bisphenol F type epoxy resins such as the product name "YDF-175S" (manufactured by Tohto Kasei Co., Ltd.), brominated bisphenol A type epoxy resins such as the product name "YDB-715" (manufactured by Tohto Kasei Co., Ltd.), bisphenol S type epoxy resins such as the product name "EPICLON EXA1514" (manufactured by DIC Corporation), hydroquinone type epoxy resins such as the product name "YDC-1312" (manufactured by Tohto Kasei Co., Ltd.), Naphthalene type epoxy resins such as "EXA4032", "HP-4770", "HP-4700", and "HP-5000" (manufactured by DIC Corporation); biphenyl type epoxy resins such as "Epicoat YX4000H" (manufactured by Japan Epoxy Resins Co., Ltd.); bisphenol A type novolac epoxy resins such as "Epicoat 157S70" (manufactured by Japan Epoxy Resins Co., Ltd.); phenol novolac type epoxy resins such as "Epicoat 154" (manufactured by Japan Epoxy Resins Co., Ltd.) and "YDPN-638" (manufactured by Tohto Kasei Co., Ltd.); cresol novolac type epoxy resins such as "YDCN-701" (manufactured by Tohto Kasei Co., Ltd.);Dicyclopentadiene phenol type epoxy resins such as HP-7200 and HP-7200H (manufactured by DIC Corporation), trishydroxyphenylmethane type epoxy resins such as Epicoat 1032H60 (manufactured by Japan Epoxy Resins), trifunctional epoxy resins such as VG3101M80 (manufactured by Mitsui Chemicals), tetraphenylolethane type epoxy resins such as Epicoat 1031S (manufactured by Japan Epoxy Resins), tetrafunctional epoxy resins such as Denacol EX-411 (manufactured by Nagase Chemical Industries, Ltd.), and ST Examples of suitable epoxy resins include hydrogenated bisphenol A type epoxy resins such as "Epicoat 190P" (manufactured by Japan Epoxy Resins Co., Ltd.), glycidyl ester type epoxy resins such as "YH-434" (manufactured by Tohto Kasei Co., Ltd.), glycidyl amine type epoxy resins such as "YH-434" (manufactured by Tohto Kasei Co., Ltd.), glyoxal type epoxy resins such as "YDG-414" (manufactured by Tohto Kasei Co., Ltd.), alicyclic polyfunctional epoxy compounds such as "Epolead GT-401" (manufactured by Daicel Chemical Industries, Ltd.), and heterocyclic type epoxy resins such as triglycidyl isocyanate (TGIC). If necessary, an epoxy reactive diluent such as "Neotohto E" (manufactured by Tohto Kasei Co., Ltd.) can be mixed in.
[0116] In addition, examples of multifunctional epoxy resins that can be used include "FINDIC A-247S", "FINDIC A-254", "FINDIC A-253", "FINDIC A-229-30A", "FINDIC A-261", "FINDIC A249", "FINDIC A-266", "FINDIC A-241", "FINDIC M-8020", "EPICLON N-740", "EPICLON N-770", "EPICLON N-865", and "EPICLON EXA-4850-150" (product names) manufactured by DIC Corporation.
[0117] The weight average molecular weight of the thermosetting resin may be 750 or more, 1000 or more, or 2000 or more from the viewpoint of easily obtaining an appropriate viscosity for the ink composition, from the viewpoint of good curability of the ink composition, and from the viewpoint of improving the solvent resistance and abrasion resistance of the pixel portion (cured product of the ink composition). From the viewpoint of obtaining an appropriate viscosity for the ink composition, it may be 500000 or less, 300000 or less, or 200000 or less. However, this does not apply to the molecular weight after crosslinking.
[0118] The content of the thermosetting resin may be 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more relative to the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of easily obtaining an appropriate viscosity as an ink composition, the viewpoint of good curability of the ink composition, and the viewpoint of improving the solvent resistance and abrasion resistance of the pixel portion (cured product of the ink composition). The content of the thermosetting resin may be 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less relative to the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of not increasing the viscosity of the ink composition too much and not making the thickness of the pixel portion too thick for the light conversion function.
[0119] [Hardening agent] Examples of the curing agent used to cure the thermosetting resin include acid anhydrides, phenolic compounds, and amine compounds. These curing agents may be used alone or in combination of two or more. The curing agent preferably includes at least one selected from the group consisting of acid anhydrides, phenolic compounds, and amine compounds. In addition, when an epoxy resin is used as the thermosetting resin, it may be self-polymerized using onium salts, organometallic complexes, tertiary amines, imidazoles, and the like.
[0120] Examples of acid anhydrides (acid anhydride-based curing agents) include 4-methylcyclohexane-1,2-dicarboxylic anhydride (4M-HHPA), 3-methylcyclohexane-1,2-dicarboxylic anhydride, cyclohexane-1,2-dicarboxylic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, 3-methyl-1,2,3,6-tetrahydrophthalic anhydride, 4-methyl-1,2,3,6-tetrahydrophthalic anhydride, bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, methyl-3,6 endomethylene-1,2,3,6-tetrahydrophthalic anhydride, 3,6 endomethylene-1,2,3,6-tetrahydrophthalic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and maleic anhydride.
[0121] Examples of phenolic compounds (phenolic hardeners) include bisphenol A, bisphenol F, bisphenol S, resorcin, catechol, hydroquinone, fluorene bisphenol, 4,4'-biphenol, 4,4',4"-trihydroxytriphenylmethane, naphthalene diol, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, calixarene, novolac-type phenolic resins (e.g., polyhydric phenol novolac resins synthesized from polyhydric hydroxy compounds represented by phenol novolac resins, cresol novolac resins, bisphenol A novolac resins, bisphenol S novolac resins, and resorcin novolac resins and formaldehyde, naphthol-phenol co-condensed novolac resins, naphthol-cresol co-condensed novolac resins, naphthol novolac resins, and alkoxy group-containing aromatic ring-modified novolac resins (polyhydric phenol compounds in which a phenol nucleus and an alkoxy group-containing aromatic ring are linked by formaldehyde). ), aralkyl type phenol resin (for example, phenol aralkyl resin such as Zylok resin and naphthol aralkyl resin), aromatic hydrocarbon formaldehyde resin modified phenol resin, dicyclopentadiene phenol addition type resin, trimethylolmethane resin, tetraphenylolethane resin, biphenyl modified phenol resin (polyhydric phenol compound in which phenol nuclei are linked by bismethylene groups), biphenyl modified naphthol resin (polyhydric naphthol compound in which phenol nuclei are linked by bismethylene groups), aminotriazine modified phenol resin (polyhydric phenol compound in which phenol nuclei are linked by melamine, benzoguanamine, etc.), and other polyhydric phenol compounds. From the viewpoint of excellent effect of improving external quantum efficiency, it is preferable that the phenol-based compound contains a novolac type phenol resin. As the novolac type phenol resin, phenol novolac resin, cresol novolac resin, and bisphenol A novolac resin are preferably used.
[0122] Specific examples of novolac-type phenolic resins include "PHENOLITE TD-2131" and "PHENOLITE TD-2090" (product names) manufactured by DIC Corporation, and "GPH-65" and "GPH-103" (product names) manufactured by Nippon Kayaku Co., Ltd.
[0123] Examples of amine compounds (amine curing agents) include aliphatic polyamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and pentaethylenehexamine; aromatic polyamines such as metaxylylenediamine, diaminodiphenylmethane, and phenylenediamine; alicyclic polyamines such as 1,3-bis(aminomethyl)cyclohexane, isophoronediamine, and norbornanediamine; and polyamide resins synthesized from dicyandiamide and a dimer of linoleic acid and ethylenediamine.
[0124] From the viewpoint of the heat resistance of the external quantum efficiency of the cured product of the ink composition, an acid anhydride-based curing agent is preferable, and from the viewpoints of the curability of the cured product of the ink composition and the viscosity stability of the ink composition, a phenol-based curing agent is preferable.
[0125] The content of the curing agent may be, for example, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less, relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition. The content of the curing agent may be, for example, 1 part by mass or more, or 3 parts by mass or more, relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition.
[0126] [Cure accelerator (curing catalyst)] Examples of the curing accelerator (curing catalyst) used to cure the thermosetting resin include phosphorus compounds, tertiary amine compounds, imidazole compounds, organic acid metal salts, Lewis acids, and amine complex salts. Examples of the phosphorus compounds include triphenylphosphine, tri-para-tolylphosphine, diphenylcyclohexylphosphine, and methyltributylphosphonium iodide. Examples of the tertiary amine compounds include N,N-dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and tris(dimethylaminomethyl)phenol. Examples of the imidazole compounds include 1-cyanoethyl-2-ethyl-4-methylimidazole and 2-ethyl-4-methylimidazole.
[0127] The thermosetting resin may be alkali-insoluble from the viewpoint of easily obtaining a pixel portion (cured product of the ink composition) with excellent reliability. The thermosetting resin being alkali-insoluble means that the amount of the thermosetting resin dissolved in a 1% by mass aqueous potassium hydroxide solution at 25°C is 30% by mass or less based on the total mass of the thermosetting resin. The amount of the thermosetting resin dissolved is preferably 10% by mass or less, more preferably 3% by mass or less.
[0128] In this embodiment, the ink composition may contain at least one of a photopolymerizable compound and a thermosetting resin, and may contain both a photopolymerizable compound and a thermosetting resin. When the ink composition contains a photopolymerizable compound, it may not contain a thermosetting resin. When the ink composition contains a thermosetting resin, it may not contain a photopolymerizable compound. From the viewpoint of the storage stability of the ink composition containing luminescent nanocrystalline particles (e.g., quantum dots) and the durability (humid heat stability, etc.) of the pixel portion (cured product of the ink composition), it is preferable to use a thermosetting resin among the photopolymerizable compound and the thermosetting resin, and from the viewpoint of the storage stability of the ink composition containing luminescent nanocrystalline particles (e.g., quantum dots) and the ability to cure at a low temperature where the quantum dots are less susceptible to deterioration due to heating, it is more preferable to use a photoradical polymerizable compound, and from the viewpoint of being able to form a pixel portion (cured product of the ink composition) without being inhibited by oxygen in the curing process, it is preferable to use a photocationic polymerizable compound.
[0129] When the ink composition contains a photopolymerizable compound and a thermosetting resin, the total content of the photopolymerizable compound and the thermosetting resin may be 3 parts by mass or more, 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more relative to the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of easily obtaining an appropriate viscosity as an ink composition, the viewpoint of good curability of the ink composition, and the viewpoint of improving the solvent resistance and abrasion resistance of the pixel portion (cured product of the ink composition). In addition, the total content of the photopolymerizable compound and the thermosetting resin may be 60 parts by mass or less, 40 parts by mass or less, or 20 parts by mass or less relative to the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition from the viewpoint of not increasing the viscosity of the ink composition too much and not making the thickness of the pixel portion too thick for the light conversion function.
[0130] [Light scattering particles] The light-scattering particles are, for example, optically inactive inorganic fine particles. When the ink composition contains the light-scattering particles, the ink composition can scatter light from a light source irradiated onto the pixel portion, thereby obtaining excellent optical properties.
[0131] Examples of materials constituting the light-scattering particles include simple metals such as tungsten, zirconium, titanium, platinum, bismuth, rhodium, palladium, silver, tin, platinum, and gold; metal oxides such as silica, barium sulfate, barium carbonate, calcium carbonate, talc, clay, kaolin, barium sulfate, barium carbonate, calcium carbonate, alumina white, titanium oxide, magnesium oxide, barium oxide, aluminum oxide, bismuth oxide, zirconium oxide, and zinc oxide; metal carbonates such as magnesium carbonate, barium carbonate, bismuth subcarbonate, and calcium carbonate; metal hydroxides such as aluminum hydroxide; complex oxides such as barium zirconate, calcium zirconate, calcium titanate, barium titanate, and strontium titanate; and metal salts such as bismuth subnitrate. From the viewpoint of excellent ejection stability and an excellent effect of improving external quantum efficiency, the light-scattering particles preferably contain at least one type selected from the group consisting of titanium oxide, alumina, zirconium oxide, zinc oxide, calcium carbonate, barium sulfate, barium titanate, and silica, and more preferably contain at least one type selected from the group consisting of titanium oxide, zirconium oxide, zinc oxide, and barium titanate.
[0132] The shape of the light-scattering particles may be spherical, filamentous, irregular, etc. However, it is preferable to use particles having a less directional particle shape (for example, spherical, regular tetrahedral, etc.) as the light-scattering particles, since this can further improve the uniformity, fluidity, and light scattering properties of the ink composition and can provide excellent ejection stability.
[0133] The average particle diameter (volume average diameter) of the light scattering particles in the ink composition may be 0.05 μm (50 nm) or more, 0.2 μm (200 nm) or more, or 0.3 μm (300 nm) or more, from the viewpoint of excellent ejection stability and excellent effect of improving external quantum efficiency. The average particle diameter (volume average diameter) of the light scattering particles in the ink composition may be 1.0 μm (1000 nm) or less, 0.6 μm (600 nm) or less, or 0.4 μm (400 nm) or less, from the viewpoint of excellent ejection stability. The average particle diameter (volume average diameter) of the light scattering particles in the ink composition may be 0.05 to 1.0 μm, 0.05 to 0.6 μm, 0.05 to 0.4 μm, 0.2 to 1.0 μm, 0.2 to 0.6 μm, 0.2 to 0.4 μm, 0.3 to 1.0 μm, 0.3 to 0.6 μm, or 0.3 to 0.4 μm. From the viewpoint of easily obtaining such an average particle diameter (volume average diameter), the average particle diameter (volume average diameter) of the light scattering particles used may be 0.05 μm or more, and may be 1.0 μm or less. In this specification, the average particle diameter (volume average diameter) of the light scattering particles in the ink composition is measured by a dynamic light scattering nanotrack particle size distribution meter and calculated by the volume average diameter. In addition, the average particle diameter (volume average diameter) of the light scattering particles used is obtained by, for example, measuring the particle diameter of each particle by a transmission electron microscope or a scanning electron microscope and calculating the volume average diameter.
[0134] The content of the light scattering particles in the ink composition may be 0.1 parts by mass or more, 1 part by mass or more, 5 parts by mass or more, 7 parts by mass or more, 10 parts by mass or more, or 12 parts by mass or more, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition, from the viewpoint of excellent effect of improving external quantum efficiency. The content of the light scattering particles may be 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 25 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition, from the viewpoint of excellent ejection stability and excellent effect of improving external quantum efficiency. When the ink composition contains a polymer dispersant, the light scattering particles can be dispersed well even when the content of the light scattering particles is relatively high (for example, about 60 parts by mass).
[0135] The mass ratio of the content of the light scattering particles to the content of the luminescent nanocrystal particles (light scattering particles / luminescent nanocrystal particles) may be 0.01 or more, 0.02 or more, 0.05 or more, 0.07 or more, 0.1 or more, 0.2 or more, or 0.5 or more, from the viewpoint of an excellent effect of improving external quantum efficiency. The mass ratio (light scattering particles / luminescent nanocrystal particles) may be 5.0 or less, 2.0 or less, or 1.5 or less, from the viewpoint of an excellent effect of improving external quantum efficiency and excellent continuous ejection property (ejection stability) during inkjet printing.
[0136] The content of the inorganic component in the ink composition (for example, the total amount of the luminescent nanocrystalline particles and the light scattering particles) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, the organic ligand, the photopolymerizable compound, the thermosetting resin, and the light scattering particles in the ink composition, from the viewpoint of easily obtaining an appropriate viscosity as an ink composition. The content of the inorganic component in the ink composition (for example, the total amount of the luminescent nanocrystalline particles and the light scattering particles) is preferably 80 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, the organic ligand, the photopolymerizable compound, the thermosetting resin, and the light scattering particles in the ink composition, from the viewpoint of easily obtaining an appropriate viscosity as an ink composition. The content of the inorganic component in the ink composition (for example, the total amount of the luminescent nanocrystalline particles and the light-scattering particles) may be 5 to 80 parts by mass, 10 to 50 parts by mass, or 20 to 40 parts by mass, relative to 100 parts by mass of the total content of the luminescent nanocrystalline particles, the organic ligand, the photopolymerizable compound, the thermosetting resin, and the light-scattering particles in the ink composition.
[0137] The ink composition may further contain other components in addition to the above-mentioned components, as long as the effects of the present invention are not impaired. Examples of other components include a polymer dispersant, a solvent, and an antioxidant.
[0138] [Polymer dispersant] The polymer dispersant is a polymer compound having a weight average molecular weight of 750 or more and a functional group having affinity for light scattering particles. The polymer dispersant has a function of dispersing light scattering particles. The polymer dispersant is adsorbed to the light scattering particles via a functional group having affinity for the light scattering particles, and disperses the light scattering particles in the ink composition due to electrostatic repulsion and / or steric repulsion between the polymer dispersants. The polymer dispersant is preferably bound to the surface of the light scattering particles and adsorbed to the light scattering particles, but may be bound to the surface of the luminescent nanocrystal particles and adsorbed to the luminescent nanoparticles, or may be free in the ink composition.
[0139] Examples of functional groups having affinity for light-scattering particles include acidic functional groups, basic functional groups, and nonionic functional groups. The acidic functional groups have a dissociable proton and may be neutralized with a base such as an amine or hydroxide ion, while the basic functional groups may be neutralized with an acid such as an organic acid or an inorganic acid.
[0140] Examples of acidic functional groups include carboxyl groups (-COOH), sulfo groups (-SO3H), sulfate groups (-OSO3H), phosphonic acid groups (-PO(OH)3), phosphoric acid groups (-OPO(OH)3), phosphinic acid groups (-PO(OH)-), and mercapto groups (-SH).
[0141] Examples of basic functional groups include primary, secondary and tertiary amino groups, ammonium groups, imino groups, and nitrogen-containing heterocyclic groups such as pyridine, pyrimidine, pyrazine, imidazole and triazole.
[0142] Examples of the nonionic functional group include a hydroxy group, an ether group, a thioether group, a sulfinyl group (-SO-), a sulfonyl group (-SO2-), a carbonyl group, a formyl group, an ester group, a carbonate ester group, an amide group, a carbamoyl group, a ureido group, a thioamide group, a thioureido group, a sulfamoyl group, a cyano group, an alkenyl group, an alkynyl group, a phosphine oxide group, and a phosphine sulfide group.
[0143] The polymeric dispersant may be a polymer (homopolymer) of a single monomer, or a copolymer (copolymer) of multiple types of monomers. The polymeric dispersant may be any of a random copolymer, a block copolymer, or a graft copolymer. When the polymeric dispersant is a graft copolymer, it may be a comb-shaped graft copolymer or a star-shaped graft copolymer. The polymeric dispersant may be, for example, an acrylic resin, a polyester resin, a polyurethane resin, a polyamide resin, a polyether, a phenolic resin, a silicone resin, a polyurea resin, an amino resin, an epoxy resin, a polyamine such as polyethyleneimine and polyallylamine, or a polyimide.
[0144] As the polymer dispersant, commercially available products can be used. Examples of commercially available products that can be used include the Ajisper PB series manufactured by Ajinomoto Fine-Techno Co., Ltd., the DISPERBYK series and BYK series manufactured by BYK, and the Efka series manufactured by BASF.
[0145] Commercially available polymer dispersants include, for example, “DISPERBYK-130”, “DISPERBYK-161”, “DISPERBYK-162”, “DISPERBYK-163”, “DISPERBYK-164”, “DISPERBYK-166”, “DISPERBYK-167”, “DISPERBYK-168”, “DISPERBYK-170”, “DISPERBYK-171”, “DISPERBYK-174”, “DISPERBYK-180”, “DISPERBYK-182”, “DISPERBYK-183”, “DISPERBYK-184”, “DISPERBYK-185”, “DISPERBYK-2000”, “DISPERBYK-2001”, “DISPERBYK-2008”, “DISPERBYK-2009”, “DISPERBYK-2020”, “DISPERBYK-2031”, “DISPERBYK-2032”, “DISPERBYK-2033”, “DISPERBYK-2034”, “DISPERBYK-2035”, “DISPERBYK-2036”, “DISPERBYK-2037”, “DISPERBYK-2038”, “DISPERBYK-2039”, “DISPERBYK-2040”, “DISPERBYK-2041”, “DISPERBYK-2042”, “DISPERBYK-2043”, “DISPERBYK-2044”, “DISPERBYK-2045”, “DISPERBYK-2046”, “DISPERBYK-2047”, “DISPERBYK-2048”, “DISPERBYK-2049”, “DISPERBYK-2050”, “DISPERBYK-2051”, “DISPERBYK-20 "BYK-2022", "DISPERBYK-2025", "DISPERBYK-2050", "DISPERBYK-2070", "DISPERBYK-2096", "DISPERBYK-2150", "DISPERBYK-2155", "DISPERBYK-2163", "DISPERBYK-2164", "BYK-LPN21116" and "BYK-LPN6919"; "EFKA" from BASF 4010'', ``EFKA4015'', ``EFKA4046'', ``EFKA4047'', ``EFKA4061'', ``EFKA4080'', ``EFKA4300'', ``EFKA4310'', ``EFKA4320'', "EFKA4330", "EFKA4340", "EFKA4560", "EFKA4585", "EFKA5207", "EFKA1501", "EFKA1502", "EFKA1503" and "EFKA PX-4701”;Solsperse 3000, Solsperse 9000, Solsperse 13240, Solsperse 13650, Solsperse 13940, Solsperse 11200, Solsperse 13940, Solsperse 16000, Solsperse 17000, Solsperse 18000, Solsperse 20000, Solsperse 21000, Solsperse 24000, Solsperse 26000, Solsperse 27000, Solsperse 28000, Solsperse 32000, Solsperse 32500, Solsperse 3255 manufactured by Lubrizol 0", "Solsperse 32600", "Solsperse 33000", "Solsperse 34750", "Solsperse 35100", "Solsperse 35200", "Solsperse 36000", "Solsperse 37500", "Solsperse 38500", "Solsperse 39000", "Solsperse 41000", "Solsperse 54000", "Solsperse 71000" and "Solsperse 76500" manufactured by Ajinomoto Fine-Techno Co., Ltd.; "Ajisper PB821", "Ajisper PB822", "Ajisper PB881", "PN411" and "PA111" manufactured by Evonik; Dispers650, TEGO Dispers660C, TEGO Dispers662C, TEGO Dispers670, TEGO Dispers685, TEGO Dispers700, TEGO Dispers710 and TEGO Dispers760W; Disparlon DA-703-50, DA-705 and DA-725 manufactured by Kusumoto Chemicals can be used.
[0146] [solvent] Examples of the solvent include ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol dibutyl ether, diethyl adipate, dibutyl oxalate, dimethyl malonate, diethyl malonate, dimethyl succinate, diethyl succinate, 1,4-butanediol diacetate, and glyceryl triacetate.
[0147] From the viewpoint of continuous ejection of the ink composition, the boiling point of the solvent under atmospheric pressure is preferably 150° C. or higher, and more preferably 180° C. or higher. In addition, since it is necessary to remove the solvent from the ink composition before curing the ink composition when forming a pixel portion, from the viewpoint of easy removal of the solvent, the boiling point of the solvent under atmospheric pressure is preferably 300° C. or lower.
[0148] In the ink composition of this embodiment, the photopolymerizable compound also functions as a dispersion medium, so that it is possible to disperse the light-scattering particles and the luminescent nanocrystalline particles without using a solvent, which has the advantage that a step of removing the solvent by drying is not required when forming the pixel portion.
[0149] [Antioxidants] The ink composition may further contain an antioxidant. In this case, the quantum yield can be improved and the decrease in quantum yield over time can be further suppressed. The antioxidant may be, for example, a phosphite compound, a thioether compound, etc., and is preferably a phosphite compound from the viewpoint of improving the quantum yield and further suppressing the decrease in quantum yield over time.
[0150] The antioxidant may be a phosphite triester compound. The phosphite triester compound may be a compound represented by the following formula (2).
[0151] [ka]
[0152] In formula (2), R 1 , R 2 and R 3 R each independently represents a monovalent organic group. 1 , R 2 and R 3 Two selected from the group may be bonded to each other to form a ring.
[0153] Specific examples of the compound represented by formula (2) include triphenyl phosphite (triphenyl phosphite), 2-ethylhexyl diphenyl phosphite, and diphenyl octyl phosphite.
[0154] The phosphite triester compound may be liquid or solid at room temperature (25° C.), but is preferably liquid at room temperature (25° C.) from the viewpoints of fully satisfying the performance requirement specific to an ink composition, namely compatibility with other components in the ink composition (such as a photopolymerizable compound), and further suppressing a decrease in the quantum yield of the ink composition. The melting point of the phosphite triester compound may be 20° C. or lower, or 10° C. or lower.
[0155] The content of the antioxidant may be 0.01 parts by mass or more, 0.1 parts by mass or more, 1 part by mass or more, or 5 parts by mass or more, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition, from the viewpoint of suppressing the decrease in the quantum yield of the ink composition. Even a small amount of the antioxidant can be added to more effectively suppress the decrease in quantum yield, so the content of the antioxidant is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the total content of the luminescent nanocrystalline particles, organic ligand, photopolymerizable compound, thermosetting resin, and light scattering particles in the ink composition. When the content of the antioxidant is within the above range, in addition to being able to ensure better film strength during the formation of the coating film, the antioxidant is more effectively suppressed from bleeding onto the surface, and good optical properties can be ensured.
[0156] When the ink composition contains a photopolymerizable compound, the content of the antioxidant may be 0.01 parts by mass or more, 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, or 3 parts by mass or more, relative to 100 parts by mass of the photopolymerizable compound, from the viewpoint of further suppressing the decrease in the quantum yield of the ink composition. Since the decrease in the quantum yield can be more effectively suppressed even with a small amount of addition, the content of the antioxidant may be 10 parts by mass or less, 7 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of the photopolymerizable compound. When the content of the antioxidant is within the above range, in addition to being able to ensure better film strength during the formation of the coating film, there is a tendency that the antioxidant is more suppressed from bleeding to the surface and good optical properties can be ensured.
[0157] The viscosity of the ink composition described above at the ink temperature during inkjet printing (for example, in a temperature range of 25 to 40° C.) may be, for example, 2 mPa·s or more, 5 mPa·s or more, or 7 mPa·s or more, from the viewpoint of ejection stability during inkjet printing. The viscosity of the ink composition at the ink temperature during inkjet printing (for example, in a temperature range of 25 to 40° C.) may be 20 mPa·s or less, 15 mPa·s or less, or 12 mPa·s or less. The viscosity of the ink composition at the ink temperature during inkjet printing (for example, in a temperature range of 25 to 40° C.) may be, for example, 2 to 20 mPa·s, 2 to 15 mPa·s, 2 to 12 mPa·s, 5 to 20 mPa·s, 5 to 15 mPa·s, 5 to 12 mPa·s, 7 to 20 mPa·s, 7 to 15 mPa·s, or 7 to 12 mPa·s. For example, the viscosity of the ink composition at 40° C. may be in the above range. In this specification, the viscosity of the ink composition is, for example, a viscosity measured by an E-type viscometer. As the viscosity falling within the above range within a temperature range of 25 to 40°C, it is more preferable that the viscosity at 25°C is 30 mPa·s or less.
[0158] When the viscosity of the ink composition at the ink temperature during inkjet printing is 2 mPa s or more, the meniscus shape of the ink composition at the tip of the ink ejection hole of the ejection head is stable, making it easy to control the ejection of the ink composition (for example, control of the ejection amount and ejection timing).On the other hand, when the viscosity of the ink composition at the ink temperature during inkjet printing is 20 mPa s or less, the ink composition can be smoothly ejected from the ink ejection hole.
[0159] The surface tension of the ink composition is preferably suitable for the inkjet method, specifically, preferably in the range of 20 to 40 mN / m, more preferably 25 to 35 mN / m. By setting the surface tension in this range, ejection control (e.g., control of the ejection amount and the ejection timing) can be facilitated, and the occurrence of flight curvature can be suppressed. Note that flight curvature refers to the occurrence of a deviation of 30 μm or more in the landing position of the ink composition from the target position when the ink composition is ejected from the ink ejection hole. When the surface tension is 40 mN / m or less, the meniscus shape at the tip of the ink ejection hole is stable, and therefore ejection control of the ink composition (e.g., control of the ejection amount and the ejection timing) can be facilitated. On the other hand, when the surface tension is 20 mN / m or more, the surrounding area of the ink ejection hole can be prevented from being contaminated by the ink composition, and therefore the occurrence of flight curvature can be suppressed. That is, there is no risk of the ink composition not landing accurately in the pixel portion-forming region where it is intended to land, resulting in insufficient pixel portion filling, or of the ink composition landing in a pixel portion-forming region (or pixel portion) adjacent to the pixel portion-forming region where it is intended to land, resulting in reduced color reproducibility.
[0160] The ink composition of the present embodiment is preferably applied to a piezo-jet type inkjet recording device with a mechanical ejection mechanism using a piezoelectric element. In the piezo-jet type, the ink composition is not instantaneously exposed to high temperatures when ejected. Therefore, the luminescent nanocrystal particles are less likely to degrade, and the expected luminescent characteristics can be more easily obtained in the pixel portion (light conversion layer).
[0161] When the ink composition of this embodiment is prepared so that the pixel portion (light conversion layer) after curing has a light conversion layer thickness of, for example, 15 um, it is preferable that the leakage rate of blue light, which is the backlight, is 10% or less. By making the leakage rate of blue light from the pixel portion 10% or less, the color purity of each pixel portion is increased, and the color gamut of the display can be increased. The leakage rate of blue light can be measured using a general spectrometer, such as a multichannel spectrometer MCPD-9800 manufactured by Otsuka Electronics, and can be defined by the following formula.
[0162] Blue light leakage = Number of blue light photons leaking from the pixel area / Number of blue light photons entering the pixel area
[0163] The blue light has an emission peak in the range of 420 to 480 nm, and preferably has an emission peak in the range of 440 to 470 nm, or 440 to 460 nm.
[0164] In order to prevent the coating film of the ink composition from absorbing moisture in the atmosphere and to prevent the luminescence (e.g., fluorescence) of the luminescent nanocrystalline particles (quantum dots, etc.) from decreasing over time, the coating film of the ink composition is preferably alkali-insoluble in this embodiment. That is, the ink composition of this embodiment is preferably an ink composition capable of forming an alkali-insoluble coating film. Such an ink composition can be obtained by using an alkali-insoluble photopolymerizable compound and / or an alkali-insoluble thermosetting resin as the photopolymerizable compound and / or the thermosetting resin. The coating film of the ink composition being alkali-insoluble means that the amount of the coating film of the ink composition dissolved in a 1% by mass aqueous potassium hydroxide solution at 25°C is 30% by mass or less based on the total mass of the coating film of the ink composition. The above-mentioned amount of dissolution of the coating film of the ink composition is preferably 10% by mass or less, more preferably 3% by mass or less. Whether the ink composition is capable of forming an alkali-insoluble coating film can be confirmed by measuring the above-mentioned dissolution amount of a coating film having a thickness of 1 μm obtained by applying the ink composition onto a substrate and drying it under conditions of 80° C. and 3 minutes.
[0165] <Method of manufacturing ink composition> The ink composition of the above-described embodiment can be obtained, for example, by mixing the components of the ink composition described above and performing a dispersion process.
[0166] The method for producing an ink composition includes, for example, a first step of preparing a dispersion of light-scattering particles containing light-scattering particles, and a second step of mixing the dispersion of light-scattering particles and luminescent nanocrystalline particles. As the luminescent nanocrystalline particles, luminescent nanocrystalline particles having an organic ligand on their surface are used. That is, the luminescent nanocrystalline particle dispersion further contains an organic ligand. The dispersion of light-scattering particles may further contain a polymer dispersant. In this method, the dispersion of light-scattering particles may further contain a photopolymerizable compound and / or a thermosetting resin, and in the second step, the photopolymerizable compound and / or a thermosetting resin may further be mixed. According to this method, the light-scattering particles can be sufficiently dispersed. Therefore, the optical characteristics of the pixel portion can be improved, and an ink composition having excellent ejection stability can be easily obtained.
[0167] In the step of preparing a dispersion of light-scattering particles, the light-scattering particles may be mixed with, in some cases, a polymer dispersant, and a photopolymerizable compound and / or a thermosetting resin, and a dispersion treatment may be performed to prepare a dispersion of light-scattering particles. The mixing and dispersion treatment may be performed using a dispersing device such as a bead mill, a paint conditioner, a planetary agitator, or a jet mill. It is preferable to use a bead mill or a paint conditioner, since the dispersibility of the light-scattering particles is improved and the average particle size of the light-scattering particles is easily adjusted to a desired range. By mixing the light-scattering particles with a polymer dispersant before mixing the luminescent nanocrystalline particles and the light-scattering particles, the light-scattering particles can be more thoroughly dispersed. Therefore, excellent discharge stability and excellent external quantum efficiency can be obtained more easily.
[0168] The method for producing an ink composition may further include a step of preparing a dispersion of luminescent nanocrystal particles containing luminescent nanocrystal particles and an organic solvent before the second step. In this case, in the second step, a dispersion of light-scattering particles and a dispersion of luminescent nanocrystal particles are mixed. In the step of preparing a dispersion of luminescent nanocrystal particles, the luminescent nanocrystal particles may be mixed with an organic solvent and a dispersion treatment is performed to prepare a dispersion of luminescent nanocrystal particles. The mixing and dispersion treatment may be performed using a dispersion device such as a bead mill, a paint conditioner, a planetary agitator, or a jet mill. From the viewpoint that the dispersibility of the luminescent nanocrystal particles is good and the average particle size of the luminescent nanocrystal particles is easily adjusted to a desired range, it is preferable to use a bead mill, a paint conditioner, or a jet mill. According to this method, the luminescent nanocrystal particles can be sufficiently dispersed. Therefore, the optical characteristics of the pixel portion can be improved and an ink composition having excellent ejection stability can be easily obtained. In the above process, the dispersion of luminescent nanocrystalline particles may further contain a photopolymerizable compound and / or a thermosetting resin.
[0169] In this manufacturing method, the organic solvent may be added in the first step or in the second step. That is, the first step may be a step of preparing a dispersion of light-scattering particles containing light-scattering particles, a polymer dispersant, and an organic solvent, and the second step may be a step of mixing the dispersion of light-scattering particles, luminescent nanocrystalline particles, and an organic solvent.
[0170] The method for producing an ink composition may further include a step of mixing an organic solvent with a thermosetting resin and / or a photopolymerizable compound to prepare a solution containing the thermosetting resin and / or the photopolymerizable compound. In this case, in the second step, the solution containing the light scattering particle dispersion, the luminescent nanocrystalline particle dispersion, the thermosetting resin and / or the photopolymerizable compound prepared in the above step, and an organic solvent may be mixed. That is, the second step may be a step of mixing the solution containing the light scattering particle dispersion, the luminescent nanocrystalline particle dispersion, the thermosetting resin and / or the photopolymerizable compound, and an organic solvent.
[0171] In this manufacturing method, other components may be used in addition to the above-mentioned components. In this case, the other components may be contained in the luminescent nanocrystalline particle dispersion or the light-scattering particle dispersion. The other components may also be mixed into a composition obtained by mixing the luminescent nanocrystalline particle dispersion and the light-scattering particle dispersion.
[0172] <Ink composition set> An ink composition set of one embodiment includes the ink composition of the above-described embodiment. The ink composition set may include an ink composition that does not contain luminescent nanocrystalline particles (non-luminescent ink composition) in addition to the ink composition of the above-described embodiment (luminescent ink composition). The non-luminescent ink composition may be a conventionally known ink composition, and may have the same composition as the ink composition of the above-described embodiment (luminescent ink composition) except that it does not contain luminescent nanocrystalline particles.
[0173] Since the non-luminous ink composition does not contain luminous nanocrystalline particles, when light is incident on a pixel portion formed by the non-luminous ink composition (a pixel portion including a cured product of the non-luminous ink composition), the light emitted from the pixel portion has approximately the same wavelength as the incident light. Therefore, the non-luminous ink composition is suitably used for forming a pixel portion of the same color as the light from a light source. For example, when the light from the light source is light having a wavelength in the range of 420 to 480 nm (blue light), the pixel portion formed by the non-luminous ink composition can be a blue pixel portion.
[0174] The non-luminous ink composition preferably contains light-scattering particles. When the non-luminous ink composition contains light-scattering particles, the pixel portion formed by the non-luminous ink composition can scatter light incident on the pixel portion, thereby reducing the light intensity difference in the viewing angle of the light emitted from the pixel portion.
[0175] <Light conversion layer and color filter, and their manufacturing methods> Hereinafter, the details of the light conversion layer and the color filter obtained by using the ink composition set of the above-mentioned embodiment will be described with reference to the drawings. In the following description, the same or corresponding elements are designated by the same reference numerals, and duplicated descriptions will be omitted.
[0176] Fig. 1 is a schematic cross-sectional view of a color filter according to an embodiment. As shown in Fig. 1, the color filter 100 includes a base material 40 and a light conversion layer 30 provided on the base material 40. The light conversion layer 30 includes a plurality of pixel units 10 and a light shielding unit 20.
[0177] The light conversion layer 30 has a first pixel portion 10a, a second pixel portion 10b, and a third pixel portion 10c as the pixel portion 10. The first pixel portion 10a, the second pixel portion 10b, and the third pixel portion 10c are arranged in a lattice pattern so as to be repeated in this order. The light shielding portion 20 is provided between adjacent pixel portions, that is, between the first pixel portion 10a and the second pixel portion 10b, between the second pixel portion 10b and the third pixel portion 10c, and between the third pixel portion 10c and the first pixel portion 10a. In other words, these adjacent pixel portions are separated by the light shielding portion 20.
[0178] The first pixel portion 10a and the second pixel portion 10b are luminescent pixel portions (luminescent pixel portions) each including a cured product of the ink composition of the above-mentioned embodiment. The cured product includes luminescent nanocrystalline particles, a curing component, and light scattering particles. The curing component is a component obtained by polymerization of a photopolymerizable compound and / or curing (polymerization, crosslinking, etc.) of a thermosetting resin, and includes a polymer of a photopolymerizable compound and / or a cured product of a thermosetting resin. That is, the first pixel portion 10a includes a first curing component 13a, and a first luminescent nanocrystalline particle 11a and a first light scattering particle 12a each dispersed in the first curing component 13a. Similarly, the second pixel portion 10b includes a second curing component 13b, and a second luminescent nanocrystalline particle 11b and a second light scattering particle 12b each dispersed in the second curing component 13b. In the first pixel portion 10a and the second pixel portion 10b, the first curing component 13a and the second curing component 13b may be the same or different, and the first light-scattering particles 12a and the second light-scattering particles 12b may be the same or different.
[0179] The first luminescent nanocrystalline particles 11a are red luminescent nanocrystalline particles that absorb light with a wavelength in the range of 420 to 480 nm and emit light with a peak emission wavelength in the range of 605 to 665 nm. That is, the first pixel portion 10a may be rephrased as a red pixel portion for converting blue light to red light. The second luminescent nanocrystalline particles 11b are green luminescent nanocrystalline particles that absorb light with a wavelength in the range of 420 to 480 nm and emit light with a peak emission wavelength in the range of 500 to 560 nm. That is, the second pixel portion 10b may be rephrased as a green pixel portion for converting blue light to green light. It is preferable that the ink composition containing Ag, In, Ga, and S of the present invention is used for the green luminescent pixel portion.
[0180] The total content of the luminescent nanocrystal particles and the organic ligand in the luminescent pixel section is 10 mass% or more, based on the total mass of the luminescent pixel section, and may be 15 mass% or more, 21 mass% or more, 25 mass% or more, 27 mass% or more, 30 mass% or more, 35 mass% or more, 40 mass% or more, 45 mass% or more, or 50 mass% or more, and may be 70 mass% or less, 65 mass% or less, 60 mass% or less, or 55 mass% or less.
[0181] The content of the light-scattering particles in the luminescent pixel section may be 0.1% by mass or more, 1% by mass or more, 3% by mass or more, or 5% by mass or more based on the total mass of the luminescent pixel section, from the viewpoint of a more excellent effect of improving external quantum efficiency. The content of the light-scattering particles may be 60% by mass or less, 50% by mass or less, 40% by mass or less, or 30% by mass or less based on the total mass of the luminescent pixel section, from the viewpoint of a more excellent effect of improving external quantum efficiency and from the viewpoint of excellent reliability of the pixel section.
[0182] The third pixel portion 10c is a non-luminous pixel portion (non-luminous pixel portion) containing a cured product of the non-luminous ink composition described above. The cured product does not contain luminous nanocrystalline particles, but contains light scattering particles and a curing component. The curing component is, for example, a component obtained by polymerization of a photopolymerizable compound and / or curing (polymerization, crosslinking, etc.) of a thermosetting resin, and contains a polymer of a photopolymerizable compound and / or a cured product of a thermosetting resin. That is, the third pixel portion 10c contains a third curing component 13c and third light scattering particles 12c dispersed in the third curing component 13c. The third light scattering particles 12c may be the same as or different from the first light scattering particles 12a and the second light scattering particles 12b.
[0183] The third pixel unit 10c has a transmittance of 30% or more for light with a wavelength in the range of 420 to 480 nm, for example. Therefore, when a light source that emits light with a wavelength in the range of 420 to 480 nm is used, the third pixel unit 10c functions as a blue pixel unit. The transmittance of the third pixel unit 10c can be measured by a microspectrometer.
[0184] The content of the light-scattering particles in the non-luminous pixel portion may be 1 mass % or more, 5 mass % or more, or 10 mass % or more based on the total mass of the non-luminous pixel portion from the viewpoint of further reducing the light intensity difference at the viewing angle. The content of the light-scattering particles may be 80 mass % or less, 75 mass % or less, or 70 mass % or less based on the total mass of the non-luminous pixel portion from the viewpoint of further reducing light reflection.
[0185] The thickness of the pixel portion (first pixel portion 10a, second pixel portion 10b, and third pixel portion 10c) may be, for example, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, or 6 μm or more, and may be 30 μm or less, or 20 μm or less.
[0186] The light shielding portion 20 is a so-called black matrix that is provided to separate adjacent pixel portions to prevent color mixing and to prevent light leakage from a light source. The material constituting the light shielding portion 20 is not particularly limited, and in addition to metals such as chromium, cured products of resin compositions containing light shielding particles such as carbon fine particles, metal oxides, inorganic pigments, and organic pigments in a binder polymer, etc. can be used. As the binder polymer used here, one or more mixtures of resins such as polyimide resin, acrylic resin, epoxy resin, polyacrylamide, polyvinyl alcohol, gelatin, casein, and cellulose, photosensitive resin, and O / W emulsion type resin composition (for example, an emulsion of reactive silicone), etc. can be used. The thickness of the light shielding portion 20 may be, for example, 0.5 μm or more and 10 μm or less.
[0187] The substrate 40 is a transparent substrate having optical transparency, and can be, for example, a transparent glass substrate such as quartz glass, Pyrex (registered trademark) glass, or a synthetic quartz plate, or a transparent flexible substrate such as a transparent resin film or an optical resin film. Among these, it is preferable to use a glass substrate made of alkali-free glass that does not contain an alkali component in the glass. Specifically, Corning's "7059 Glass", "1737 Glass", "Eagle 200" and "Eagle XG", Asahi Glass's "AN100", and Nippon Electric Glass's "OA-10G" and "OA-11" are suitable. These materials have a small coefficient of thermal expansion and are excellent in dimensional stability and workability in high-temperature heat treatment.
[0188] The color filter 100 including the above-described light conversion layer 30 is suitably used when using a light source that emits light with a wavelength in the range of 420 to 480 nm.
[0189] A manufacturing method for the light conversion layer 30 (color filter 100) according to one embodiment includes a step of forming a light-shielding portion 20 on a substrate 40 (light-shielding portion forming step), a step of disposing the ink composition of the above-mentioned embodiment in a pixel portion forming region partitioned by the light-shielding portion 20 on the substrate 40 by an inkjet method (disposing step), and a step of curing the ink composition (curing step).
[0190] In the light shielding portion forming step, the light shielding portion 20 is formed in a pattern (for example, a lattice shape). The light shielding portion 20 can be formed by forming a thin metal film such as chromium or a thin film of a resin composition containing light shielding particles on one side of the substrate 40, and patterning the thin film. The thin metal film can be formed by, for example, a sputtering method or a vacuum deposition method. The thin film of a resin composition containing light shielding particles can be formed by, for example, a coating method or a printing method. The patterning method can be, for example, a photolithography method.
[0191] In the disposing step, the ink composition is selectively disposed (adhered) to a pixel portion forming region (a region on the substrate 40 where the light shielding portion 20 is not formed (opening of the light shielding portion 20)) by an inkjet method. Examples of the inkjet method include a bubble jet method using an electrothermal converter as an energy generating element, and a piezo jet method using a piezoelectric element.
[0192] In the curing step, the ink composition disposed in the disposing step is cured by irradiation with active energy rays or by heating.
[0193] When the inkjet is cured by irradiation with active energy rays (e.g., ultraviolet rays), the light source may be, for example, a mercury lamp, a metal halide lamp, a xenon lamp, an LED, or the like. The wavelength of the irradiated light may be, for example, 200 nm or more and 440 nm or less. The exposure dose may be, for example, 10 mJ / cm. 2 or more, 20,000 mJ / cm 2 It may be the following:
[0194] When the ink composition is cured by heating, the heating temperature may be, for example, 110° C. or more and 250° C. or less. The heating time may be, for example, 10 minutes or more and 120 minutes or less.
[0195] When the ink composition contains a solvent (organic solvent), the manufacturing method of this embodiment may further include a step of volatilizing the solvent (volatilization step). The volatilization step is performed, for example, between the disposing step and the curing step. In the volatilization step, the ink composition is heated to volatilize the solvent. The heating temperature may be, for example, 50° C. or higher and 150° C. or lower. The heating time may be, for example, 1 minute or longer or 3 minutes or longer, and 30 minutes or shorter.
[0196] In the volatilization step, the solvent (organic solvent) may be volatilized by drying under reduced pressure (vacuum drying). The conditions for the reduced pressure drying may usually be a pressure of 1.0 to 500 Pa, at 20 to 30° C., for 3 to 30 minutes, from the viewpoint of controlling the composition of the ink composition.
[0197] Although an embodiment of the color filter and the light conversion layer, as well as the manufacturing method thereof, have been described above, the present invention is not limited to the above embodiment.
[0198] For example, the light conversion layer may have a pixel portion (blue pixel portion) containing a cured product of a luminescent ink composition containing blue luminescent nanocrystal particles instead of or in addition to the third pixel portion 10c. The light conversion layer may also have a pixel portion (e.g., a yellow pixel portion) containing a cured product of a luminescent ink composition containing nanocrystal particles that emit light of a color other than red, green, or blue. In these cases, it is preferable that each of the luminescent nanocrystal particles contained in each pixel portion of the light conversion layer has a maximum absorption wavelength in the same wavelength range.
[0199] At least a part of the pixel portion of the light conversion layer may contain a cured product of a composition containing a pigment other than the luminescent nanocrystalline particles.
[0200] The color filter may also have an ink-repellent layer made of a material having ink repellency narrower than the light-shielding portion on the pattern of the light-shielding portion. Instead of providing an ink-repellent layer, a photocatalyst-containing layer as a wettability-variable layer may be formed in a solid coating in a region including the pixel portion-forming region, and then the photocatalyst-containing layer may be exposed to light through a photomask to selectively increase the ink affinity of the pixel portion-forming region. Examples of photocatalysts include titanium oxide and zinc oxide.
[0201] The color filter may further include an ink receiving layer containing hydroxypropyl cellulose, polyvinyl alcohol, gelatin, or the like between the substrate and the pixel portion.
[0202] The color filter may also have a protective layer on the pixel portion. This protective layer is provided to flatten the color filter and prevent the components contained in the pixel portion, or the components contained in the pixel portion and the components contained in the photocatalyst-containing layer, from eluting into the liquid crystal layer. The material constituting the protective layer may be any material that is used as a known protective layer for color filters.
[0203] In addition to the above-mentioned luminescent nanocrystal particles, the pixel portion of the light conversion layer of this embodiment may further contain a pigment having approximately the same color as the luminescent color of the luminescent nanocrystal particles. In order to contain the pigment in the pixel portion, the ink composition may contain the pigment.
[0204] In addition, one or two of the red pixel portion (R), green pixel portion (G), and blue pixel portion (B) in the light conversion layer of this embodiment may be pixel portions containing a coloring material without containing luminescent nanocrystalline particles. A known coloring material can be used here, and for example, a coloring material used in the red pixel portion (R) may be a diketopyrrolopyrrole pigment and / or an anionic red organic dye. A coloring material used in the green pixel portion (G) may be at least one selected from the group consisting of a halogenated copper phthalocyanine pigment, a phthalocyanine green dye, a mixture of a phthalocyanine blue dye and an azo yellow organic dye. A coloring material used in the blue pixel portion (B) may be an ε-type copper phthalocyanine pigment and / or a cationic blue organic dye. When these coloring materials are contained in the light conversion layer, the amount of use is preferably 1 to 5 mass% based on the total mass of the pixel portion (cured product of the ink composition) from the viewpoint of preventing a decrease in transmittance. EXAMPLES
[0205] Hereinafter, the present invention will be specifically described by way of examples. However, the present invention is not limited only to the following examples. All the materials used in the examples were those in which argon gas was introduced to replace dissolved oxygen with argon gas. For titanium oxide, before mixing, it was heated at 175 °C for 4 hours under a reduced pressure of 1 mmHg and then allowed to cool in an argon gas atmosphere. The liquid materials used in the examples were dehydrated with molecular sieves 3A for 48 hours or more before mixing.
[0206] <Preparation of AIGS Nanocrystal Particle Dispersion> To the AIGS nanocrystal dispersion (AIGS QD in butyl acetate, nanocrystal dispersion concentration 35%) manufactured by Nanosys, Inc. in the United States, 4 times the amount of heptane was added to aggregate the nanocrystal particles. After precipitation by centrifugation, the nanocrystal particles were separated by decanting the supernatant. The obtained nanocrystal particles were dispersed in 1,6 - hexanediol diacrylate (manufactured by Shin - Nakamura Chemical Co., Ltd., trade name: NK Ester A - HD - N, hereinafter also referred to as "HDDA") to obtain an AIGS nanocrystal particle dispersion. The content of the luminescent nanocrystal particle concentration (including organic ligands) in the dispersion was 50% by mass. As described in SDS, the luminescent nanocrystal particles contained in the above AIGS nanocrystal dispersion were composed of silver (Ag), indium (In), gallium (Ga), and sulfur (S).
[0207] <Preparation of InP Nanocrystal Particle Dispersion> An InP nanocrystal particle dispersion was obtained in the same manner as the preparation of the AIGS nanocrystal particle dispersion, except that the nanocrystal particle dispersion was changed to the InP nanocrystal dispersion (Gen3 QD in PGMEA, ver4, nanocrystal particle dispersion concentration 30%) manufactured by Nanosys, Inc. The content of the luminescent nanocrystal particle concentration (including organic ligands) in the dispersion was 50% by mass.
[0208] <Preparation of Light - Scattering Particle Dispersion> In a container filled with argon gas, 34 g of titanium oxide (product name: CR-60-2, Ishihara Sangyo Kaisha, Ltd., average particle size (volume average diameter): 210 nm), 1.0 g of a polymer dispersant (product name: Ajisper PB-821, Ajinomoto Fine-Techno Co., Ltd.), and 35.0 g of HDDA, a light-scattering particle dispersion medium, were mixed, and zirconia beads (diameter: 1.25 mm) were added to the resulting mixture. The mixture was dispersed by shaking for 2 hours using a paint conditioner, and the zirconia beads were removed using a polyester mesh filter to obtain a light-scattering particle dispersion.
[0209] [Preparation of Ink Composition] <Example 1> 7.0g of AIGS nanocrystal dispersion, 0.7g of light scattering particle dispersion 1, 0.12g of photopolymerization initiator Omnirad TPO-H (IGM resin), 0.02g of photopolymerization initiator Omnirad 819 (IGM resin), 0.1g of antioxidant JPE-10 (Johoku Chemical Industry), and 2.1g of HDDA were mixed uniformly in a container filled with argon gas, and then the mixture was filtered through a filter with a pore size of 5 μm in a glove box. Composition 1 was prepared. The composition of the luminescent nanocrystal particles (including organic ligands), photopolymerizable compound, photopolymerizable initiator, light diffusing particles, polymer dispersant, and antioxidant in the composition was as shown in Table 1.
[0210] <Example 2> Composition 2 was prepared in the same manner as in Example 1, except that the compounding ratios of the nanocrystalline particles, photopolymerizable compound, light scattering particles, polymeric dispersant, photopolymerization initiator, and antioxidant were changed so that the composition ratios were as shown in Table 1.
[0211] <Comparative Examples 1 to 3> Compositions 3 to 5 were prepared in the same manner as in Example 1, except that an InP nanocrystal dispersion was used instead of an AIGS nanocrystal dispersion as the nanocrystal particles, and the compounding ratios of the photopolymerizable compound, light scattering particles, polymer dispersant, photopolymerization initiator, and antioxidant were changed so that the composition ratios were as shown in Table 1.
[0212] [Evaluation of optical properties] [Preparation of evaluation samples] Each composition was applied to a glass substrate in the atmosphere using a spin coater so that the film thickness was 15 μm. The applied film was then irradiated with a UV irradiator using an LED lamp with a main wavelength of 395 nm under a nitrogen atmosphere with an integrated light dose of 1500 mJ / cm. 2 The composition was cured by irradiating it with UV light so that the cured product was cured to form a layer (light conversion layer) on the glass substrate. In this way, each evaluation sample, which is a base material having a light conversion layer, was prepared.
[0213] [Evaluation of blue light leakage] A blue LED (peak emission wavelength: 450 nm) manufactured by CCS Inc. was used as the surface emission light source. The measurement device was a radiation spectrophotometer (product name "MCPD-9800") manufactured by Otsuka Electronics Co., Ltd., connected to an integrating sphere, and the integrating sphere was placed above the blue LED. A substrate having a light conversion layer prepared in the same manner as in the curing evaluation was inserted between the blue LED and the integrating sphere, and the spectrum observed when the blue LED was turned on and the illuminance at each wavelength were measured.
[0214] From the spectrum and illuminance measured by the above measuring device, the optical density (OD@450 nm) of the blue light of the cured product on the glass substrate was calculated as follows: This value indicates how much of the blue light (photons) incident on the light conversion layer was absorbed by the light conversion layer, and is an evaluation index indicating that the larger this value is, the smaller the blue leakage light is and the higher the color reproducibility of the QD-CF is.
[0215] Blue Transmittance(%)=T(Blue) / E(Blue) Film OD=-Log 10 (Blue Transmittance)
[0216] Here, T(Blue) and E(Blue) represent the following, respectively. T (Blue): The total value of "illuminance × wavelength ÷ hc" after the film is placed in the wavelength range of 380 to 490 nm. E (Blue): The total value of "illuminance × wavelength ÷ hc" before placing the film in the wavelength range of 380 to 490 nm.
[0217] [Evaluation of the viscosity of the ink composition and thickening in the air] The viscosity of the ink compositions of the examples and comparative examples was evaluated by measuring the viscosity at 25° C. using an E-type viscometer.
[0218] [Table 1]
[0219] As can be seen from the above table, the ink composition of the present invention uses luminescent nanocrystalline particles having specific constituent elements, and therefore can combine good film OD with good ink viscosity, and furthermore, can achieve excellent film OD even when a smaller amount of luminescent nanocrystalline particles is used. With conventional luminescent nanoparticles, the film OD can be increased by increasing the amount of light-diffusing particles, but this results in an increase in the ink viscosity. [Explanation of symbols]
[0220] 10...pixel portion, 10a...first pixel portion, 10b...second pixel portion, 10c...third pixel portion, 11a...first luminescent nanocrystal particle, 11b...second luminescent nanocrystal particle, 12a...first light-scattering particle, 12b...second light-scattering particle, 12c...third light-scattering particle, 20...light-shielding portion, 30...light conversion layer, 40...substrate, 100...color filter.
Claims
1. An ink composition comprising luminescent nanocrystalline particles, a photopolymerizable compound and / or a thermosetting resin, and light-scattering particles, The ink composition, wherein at least a portion of the luminescent nanocrystal particles absorb light having a wavelength in the range of 420 to 480 nm, have an emission peak in the range of 500 to 560 nm, and contain Ag, In, Ga, and S as constituent elements.
2. The ink composition according to claim 1, which has a viscosity at 25°C of 30 mPa·s or less.
3. 3. The ink composition according to claim 1, wherein when a light conversion layer having a thickness of 15 μm is formed, the leakage rate of blue light is 10% or less.
4. A liquid crystal display device comprising: a plurality of pixel units; and a light-shielding unit provided between the plurality of pixel units; The light conversion layer, wherein the plurality of pixel portions have luminescent pixel portions containing a cured product of the ink composition according to any one of claims 1 to 3.
5. A color filter comprising the light conversion layer according to claim 4 .
Citation Information
Patent Citations
Preparation method of core-shell structure quantum dot
CN102212363A
Self-luminous photosensitive resin composition, color filter manufactured therefrom, and image display device including the color filter
JP2016098375A
Ink composition, light conversion layer, and color filter
JP2018109141A
Semiconductor nanoparticle, method for producing same, and light-emitting device
JP2018141141A
Ink composition, photoconversion layer and color filter
JP2019052241A